All-solid-state lithium ion secondary battery and method for manufacturing all-solid-state lithium ion secondary battery

The laminate structure with a lithium-containing oxide and 670°C metal collector in the solid electrolyte layer addresses conductivity and adhesion issues, enhancing safety and efficiency in all-solid-state lithium-ion secondary batteries without high-temperature sintering or organic polymers.

CN119174022APending Publication Date: 2024-12-20INSTITUTE OF SCIENCE TOKYO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380039025.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2023-05-31
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing all-solid-state lithium-ion secondary batteries face challenges with insufficient lithium ion conductivity and adhesion between particles in the solid electrolyte layer, particularly with oxide-based electrolytes, which require high-temperature sintering and the use of organic polymers, compromising safety and efficiency.

Method used

The battery employs a laminate structure with a solid electrolyte layer containing a lithium-containing oxide, amorphous in nature, and a metal current collector that melts at 670°C, allowing for excellent adhesion and conductivity without high-temperature sintering or organic polymers, using a composition with specific molar ratios of lithium salt and water.

Benefits of technology

This configuration achieves higher lithium ion conductivity and enhanced safety by ensuring excellent adhesion between particles, facilitating the production of a compact and efficient all-solid-state lithium-ion secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119174022A_ABST
    Figure CN119174022A_ABST
Patent Text Reader

Abstract

An all-solid-state lithium ion secondary battery having one or more laminates in which a positive electrode layer, a solid electrolyte layer, and a negative electrode layer are arranged in this order, characterized in that: at least one of current collector layers included in at least one of the positive electrode layer and the negative electrode layer is a layer having a specific metal in a constituent material or a coating layer; the solid electrolyte layer contains an amorphous solid electrolyte containing a lithium-containing oxide containing Li, B, and O, and water and a lithium salt contained at a specific molar ratio with respect to the lithium-containing oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an all-solid-state lithium-ion secondary battery and a method for manufacturing the all-solid-state lithium-ion secondary battery. Background Art

[0002] In the past, organic solvents with high ion conductivity have been used as electrolytes in lithium-ion secondary batteries. However, organic solvents are flammable, so there are safety issues. In addition, since they are in a liquid state, it is difficult to make them compact, and when the battery becomes larger, the capacity limitation also becomes a problem.

[0003] In contrast, all-solid-state lithium-ion secondary batteries are one of the next-generation batteries that can solve these problems. The basic structure of an all-solid-state lithium-ion secondary battery is shown in FIG. Figure 1 In the embodiment of the present invention, the all-solid-state lithium-ion secondary battery 10 has a negative electrode current collector layer 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4 and a positive electrode current collector layer 5 in order from the negative electrode side. Each layer is in contact with each other and has an adjacent structure. By adopting this structure, during charging, electrons (e - ) is supplied to the negative electrode side, so that the lithium ions (Li + ) accumulates here. On the other hand, during discharge, the lithium ions (Li + ) returns to the positive electrode side through the solid electrolyte layer 3, so that the electrons are supplied to the working part 6. In the example shown in the figure, a light bulb is used as a model at the working part 6, and it is lit by discharge.

[0004] As described above, in order to obtain desired charge and discharge characteristics in an all-solid-state lithium ion secondary battery, the solid electrolyte layer needs to have excellent lithium ion conductivity.

[0005] As the solid electrolyte constituting the solid electrolyte layer, a sulfide-based solid electrolyte or an oxide-based solid electrolyte is mainly used.

[0006] Since sulfide-based solid electrolytes are soft and plastically deformable, the particles can be bonded together simply by press molding. Therefore, the interface resistance between the particles of sulfide-based solid electrolytes is low and the ion conductivity is excellent. However, sulfide-based solid electrolytes have the problem of reacting with water to produce toxic hydrogen sulfide.

[0007] In contrast, oxide-based solid electrolytes have the advantage of high safety. However, oxide-based solid electrolytes are hard and not prone to plastic deformation. In order to improve the adhesion between particles of oxide-based solid electrolytes, high-temperature sintering treatment is required, which is limited from the perspectives of battery production efficiency and energy costs. For example, Patent Document 1 discloses a solid electrolyte formed of a lithium-containing oxide composed of specific elements, and it is recorded that the solid electrolyte exhibits high ion conductivity. However, in order to use the lithium-containing oxide described in Patent Document 1 as a solid electrolyte sheet, a high-temperature sintering treatment is required.

[0008] As a technology to deal with this problem, for example, Patent Document 2 describes a composite comprising a lithium compound and lithium tetraborate, wherein the lithium compound has a lithium ion conductivity of 1.0×10 -6 S / cm or more, and the reduced two-body distribution function G(r) of the lithium tetraborate obtained from the total X-ray scattering measurement shows a specific distribution. According to the technology described in Patent Document 2, although the composite is composed of a lithium-containing oxide, lithium tetraborate undergoes plastic deformation between lithium compounds to play a role in connecting lithium compounds. Therefore, even if the composite is not subjected to a high-temperature sintering treatment, it can be formed into a lithium ion conductor showing good lithium ion conductivity by a pressurization treatment.

[0009] Previous technical literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2018-052755

[0012] Patent Document 2: International Publication No. 2021 / 193204 Summary of the invention

[0013] Technical issues to be solved by the invention

[0014] Although the composite described in the above patent document 2 is composed of lithium-containing oxide, it has a soft property and can ensure the bonding between particles even without sintering treatment and without admixing binders such as organic polymers, and has properties that cannot be achieved by oxide-based solid electrolytes to date. However, the results of research conducted by the present inventors have found that the conductivity of lithium ions is not sufficient to be practical as a solid electrolyte layer of an all-solid-state lithium-ion secondary battery at this stage, and there is room for improvement in practical application.

[0015] The object of the present invention is to provide an all-solid-state lithium-ion secondary battery, which uses a lithium-containing oxide in a solid electrolyte layer, wherein the solid electrolyte layer has excellent adhesion between particles even without high-temperature sintering treatment and, for example, without the addition of a binder such as an organic polymer, and has higher lithium ion conductivity and excellent safety, and the all-solid-state lithium-ion secondary battery has a collector layer, and the collector layer uses a metal that is difficult to use under high-temperature sintering conditions.

[0016] Furthermore, the subject of the present invention is to provide a method for manufacturing an all-solid-state lithium-ion secondary battery, which uses a lithium-containing oxide in a solid electrolyte layer, wherein the solid electrolyte layer has excellent adhesion between particles even without high-temperature sintering treatment and, for example, without the addition of a binder such as an organic polymer, and has higher lithium ion conductivity and excellent safety, and the all-solid-state lithium-ion secondary battery has a collector layer, and the collector layer uses a metal that is difficult to use under conditions of high-temperature sintering in an atmosphere containing oxygen.

[0017] Means for solving technical problems

[0018] The problems of the present invention are solved by the following means.

[0019] [1]

[0020] An all-solid-state lithium-ion secondary battery has at least one layer of a laminate, wherein the laminate is sequentially configured with a positive electrode layer, a solid electrolyte layer and a negative electrode layer, wherein:

[0021] At least one of the positive electrode layer and the negative electrode layer includes a current collector layer.

[0022] At least one of the current collector layers is a layer having a metal that melts at 670° C. under normal pressure as a constituent material, or a layer having the metal in a coating layer,

[0023] The solid electrolyte layer includes an amorphous solid electrolyte, wherein the amorphous solid electrolyte contains a lithium-containing oxide containing Li, B and O, water and a lithium salt. In the amorphous solid electrolyte, the ratio of the content of the lithium salt to the content of the lithium-containing oxide is 0.001 to 1.5 in molar ratio, and the ratio of the content of the water to the content of the lithium-containing oxide is 1 to 12 in molar ratio.

[0024] [2]

[0025] The all-solid-state lithium-ion secondary battery according to [1], wherein:

[0026] The metal that melts at 670° C. under normal pressure is Al or an Al alloy.

[0027] 〔3〕

[0028] The all-solid-state lithium-ion secondary battery according to [1] or [2], wherein:

[0029] The lithium-containing oxide comprises Li 2+x B 4+y O 7+z .

[0030] Among them, -0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3.

[0031] [4]

[0032] A method for manufacturing an all-solid-state lithium-ion secondary battery, wherein the all-solid-state lithium-ion secondary battery has at least one layer of a laminate, wherein the laminate is sequentially configured with a positive electrode layer, a solid electrolyte layer and a negative electrode layer, wherein:

[0033] At least one of the positive electrode layer and the negative electrode layer includes a current collector layer.

[0034] At least one of the above-mentioned current collector layers is a layer having Cu as a constituent material or a layer having Cu in a coating layer,

[0035] The solid electrolyte layer includes an amorphous solid electrolyte, wherein the amorphous solid electrolyte contains a lithium-containing oxide containing Li, B and O, water and a lithium salt, wherein the content of the lithium salt in the amorphous solid electrolyte is 0.001 to 1.5 in terms of molar ratio to the content of the lithium-containing oxide, and the content of the water in the amorphous solid electrolyte is 1 to 12 in terms of molar ratio to the content of the lithium-containing oxide.

[0036] The method for manufacturing an all-solid-state lithium-ion secondary battery includes the step of manufacturing a stack of the positive electrode layer, the solid electrolyte layer, and the negative electrode layer in an atmosphere containing oxygen and at 300° C. or less.

[0037] In the present invention or the specification, when a numerical range is displayed for description, when the upper limit and lower limit of the numerical range are described separately, any upper limit and lower limit can be appropriately combined as a specific numerical range. On the other hand, when a plurality of numerical ranges represented by "to" are set for description, the upper limit and lower limit forming the numerical range are not limited to the specific combination recorded before and after the "to" as a specific numerical range, and the upper limit and lower limit of each numerical range can be appropriately combined as a numerical range. In addition, in the present invention or the specification, the numerical range represented by "to" refers to a range including the numerical values ​​recorded before and after the "to" as the lower limit and upper limit.

[0038] Effects of the Invention

[0039] The all-solid-state lithium-ion secondary battery of the present invention uses a lithium-containing oxide in the solid electrolyte layer. Even if the solid electrolyte layer is not subjected to a high-temperature sintering treatment and, for example, without the addition of a binder such as an organic polymer, the adhesion between the particles is excellent, the lithium ion conductivity is higher, and the safety is also excellent. The all-solid-state lithium-ion secondary battery has a collector layer, and the collector layer uses a metal that is difficult to use under high-temperature sintering conditions.

[0040] Furthermore, in the method for manufacturing an all-solid-state lithium-ion secondary battery of the present invention, a lithium-containing oxide is used in the solid electrolyte layer. Even without a high-temperature sintering treatment and, for example, without the addition of a binder such as an organic polymer, the solid electrolyte layer has excellent adhesion between particles, higher lithium ion conductivity, and excellent safety. This enables the manufacture of an all-solid-state lithium-ion secondary battery having a current collector layer using a metal that is difficult to use under high-temperature sintering conditions in an atmosphere containing oxygen. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a cross-sectional view schematically showing an example of the structure of an all-solid-state lithium-ion secondary battery.

[0042] Figure 2 This is a diagram showing an example of an X-ray diffraction pattern for explaining the X-ray diffraction characteristics of the solid electrolyte (I) used in the present invention.

[0043] Figure 3 This is a diagram showing an example of the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (I) used in the present invention.

[0044] Figure 4 The solid electrolyte (I) used in the present invention is solidified at 20°C or 120°C. 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.

[0045] Figure 5 It means that the solid state of lithium tetraborate crystals is carried out at 20℃ or 120℃ 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.

[0046] Figure 6 The solid electrolyte (I) used in the present invention is solidified at 20°C. 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.

[0047] Figure 7 Yes Figure 6 Figure 2 shows the peak waveform separation.

[0048] Figure 8 This is a diagram showing an example of the Raman spectrum of the solid electrolyte (I) used in the present invention.

[0049] Fig. 9 This is a diagram showing the Raman spectrum of lithium tetraborate crystals.

[0050] Fig.10 Graph showing the reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of powdered Li2B4O7 crystals.

[0051] Fig.11 This is a diagram showing the X-ray diffraction pattern of powdered Li2B4O7 crystals. DETAILED DESCRIPTION

[0052] [All-solid-state lithium-ion secondary battery]

[0053] The all-solid-state lithium-ion secondary battery of the present invention (hereinafter, also referred to as "the secondary battery of the present invention") is a laminate having at least one layer, wherein the laminate is an all-solid-state lithium-ion secondary battery in which a positive electrode layer, a solid electrolyte layer and a negative electrode layer are sequentially arranged, wherein at least one of the positive electrode layer and the negative electrode layer includes a collector layer, and at least one of the collector layers is a layer having a metal melted at normal pressure and 670°C as a constituent material or a layer having the metal in a coating. The solid electrolyte layer includes a solid electrolyte (I) of a specific composition in an amorphous state described later.

[0054] In the secondary battery of the present invention, since the solid electrolyte (I) of the specific composition described later has excellent particle bonding properties, it is possible to bond the particles by processing and molding (non-sintering) without relying on the high-temperature sintering process required in the manufacture of secondary batteries using conventional oxide-based solid electrolytes, thereby manufacturing a battery having high ion conductivity (10 -3 Therefore, a secondary battery can be provided, wherein the constituent material of the current collector layer or the coating layer contains a metal that melts under conditions of high temperature sintering and is difficult to use, and melts at 670°C under normal pressure.

[0055] The structure of the secondary battery of the present invention is not particularly limited as long as it has at least one or more laminated bodies formed by sequentially configuring a positive electrode layer, a solid electrolyte layer and a negative electrode layer, including a structure formed by stacking a plurality of these layers in a manner of configuring a solid electrolyte layer between adjacent positive electrode layers and negative electrode layers (structure of a small laminated battery). Each structural layer (including a collector layer, etc.) constituting the secondary battery of the present invention can be a single-layer structure or a multi-layer structure.

[0056] Regarding the structure of the above-mentioned small stacked battery, in addition to setting the solid electrolyte layer to a solid electrolyte (I) of a specific composition, at least one of the positive electrode layer and the negative electrode layer includes a collector layer, and at least one of the collector layers has a layer having a metal that melts at normal pressure and 670°C as a constituent material or a layer having the metal in a coating, for example, the structure of the solid-state battery described in paragraphs

[0021] to

[0046] of Japanese Patent Gazette No. 2016-001602 can be referred to and applied to the present invention.

[0057] Hereinafter, each layer of the secondary battery of the present invention will be described.

[0058] <Solid electrolyte layer>

[0059] The solid electrolyte layer constituting the secondary battery of the present invention is a layer formed by forming a solid electrolyte of a specific composition in an amorphous state or a mixture of the solid electrolyte and other components into a layer. The solid electrolyte of a specific composition in an amorphous state contains a lithium-containing oxide containing Li, B and O (hereinafter also referred to as "lithium-containing oxide"), water and a lithium salt.

[0060] In the solid electrolyte of the specific composition in the amorphous state, the ratio of the content of the lithium salt to the content of the lithium-containing oxide (lithium salt / lithium-containing oxide) is 0.001 to 1.5 in terms of molar ratio. In addition, in the solid electrolyte of the specific composition in the amorphous state, the ratio of the content of water to the content of the lithium-containing oxide (water / lithium-containing oxide) is 1 to 12 in terms of molar ratio.

[0061] Hereinafter, a solid electrolyte of a specific composition in an amorphous state in which the ratios of the content of lithium salt to the content of lithium-containing oxide and the content of water to the content of lithium-containing oxide satisfy the above-mentioned specific molar ratios is also referred to as "solid electrolyte (I)". Solid electrolyte (I) is generally an inorganic solid electrolyte.

[0062] The solid electrolyte (I) is in an amorphous state (same meaning as non-crystalline state or amorphous state) and shows elastic properties that are prone to plastic deformation. As a result, in a structural layer such as a solid electrolyte layer containing a solid electrolyte (I) formed by a pressurization treatment, the adhesion between the solid electrolytes (I) and / or the adhesion between the solid electrolyte (I) and other components present in the structural layer is improved, and the interface resistance can be reduced, thereby obtaining a more excellent ion conductivity. By using the solid electrolyte (I), although it is an oxide-based solid electrolyte with high safety, even if a high-temperature sintering treatment is not performed, a structural layer such as a solid electrolyte layer showing excellent lithium ion conductivity can be formed by a pressurization treatment, etc.

[0063] The water contained in the solid electrolyte (I) at least includes bound water. Although the reason why the solid electrolyte (I) exhibits high lithium ion conductivity is not clear, in the solid electrolyte (I), a soft hydration layer is easily formed on the surface of the lithium-containing oxide, and a large amount of lithium derived from the lithium salt is contained in the hydration layer, and as a result, it is believed that the ion conductivity is further improved.

[0064] Here, in the present invention or the specification, "bound water" refers to water other than water existing as free water, or OH groups bonded to lithium-containing oxides. Even if the solid electrolyte (I) contains water in the above-mentioned content ratio, it is in the state of solid particles (including the state in which the solid particles are bonded to each other) and functions as a solid electrolyte of an all-solid-state lithium-ion secondary battery. That is, the solid electrolyte (I) contains bound water that is not removed or difficult to remove under normal drying conditions. In addition, as long as the solid electrolyte (I) functions as a solid electrolyte of an all-solid-state lithium-ion secondary battery in the state of solid particles (a state that can be processed in the state of powder), the solid electrolyte (I) may contain free water. That is, in the present invention, if the solid electrolyte can be treated as a solid particle (solid powder), "all-solid-state lithium-ion secondary battery" also includes a mode in which the solid electrolyte contains water. Moreover, the solid electrolyte (I) used in the present invention, in which the ratio of the water content to the content of the lithium-containing oxide is less than 12 in molar ratio, is not in any state of paste and gel, but in the state of solid particles (solid powder).

[0065] In the present invention, the solid electrolyte (I) being in an "amorphous state" means that it satisfies the following X-ray diffraction characteristics.

[0066] (X-ray diffraction characteristics)

[0067] In the X-ray diffraction pattern of the solid electrolyte (I) obtained from X-ray diffraction measurement using CuKα rays, a first peak having a peak top located in the range of a diffraction angle 2θ of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, a second peak having a peak top located in the range of a diffraction angle 2θ of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, a third peak having a peak top located in the range of a diffraction angle 2θ of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and a fourth peak having a peak top located in the range of a diffraction angle 2θ of 34.4 to 34.8° and a full width at half maximum of 0.65° or less are not present, or

[0068] In the X-ray diffraction pattern, when at least one of the above-mentioned 1st peak, 2nd peak, 3rd peak and 4th peak (hereinafter referred to as "peak X") is present, the intensity ratio of at least one of the peaks X calculated by the intensity measurement method described below is 5.0 or less.

[0069] - Strength measurement method -

[0070] The arithmetic mean of Av1 and Av2 is calculated by calculating the average intensity (Av1) in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of the peak X, and calculating the average intensity (Av2) in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of the peak X. The ratio of the peak intensity at the peak top of the peak X to the arithmetic mean (peak intensity at the peak top of the peak X / arithmetic mean) is taken as the intensity ratio.

[0071] The X-ray diffraction characteristics will be described in more detail.

[0072] In the X-ray diffraction pattern of the solid electrolyte (I) obtained from the X-ray diffraction measurement using CuKα rays, when the above-mentioned first peak, second peak, third peak and fourth peak do not exist, the above-mentioned X-ray diffraction characteristics are satisfied and the solid electrolyte (I) is in an amorphous state.

[0073] Furthermore, in the X-ray diffraction pattern of the solid electrolyte (I) obtained from the X-ray diffraction measurement using CuKα rays, when the above-mentioned peak X is present, when the intensity ratio of at least one peak among the peaks X obtained by the above-mentioned intensity measurement method also satisfies 5.0 or less, the above-mentioned X-ray diffraction characteristics are also satisfied, and the solid electrolyte (I) is in an amorphous state.

[0074] Here, the full width at half maximum (FWHM) of the peak refers to the peak width (°) at a point where the peak intensity at the top of the peak is 1 / 2.

[0075] refer to Figure 2 , the above-mentioned intensity measurement method is explained in more detail.

[0076] Figure 2 This is a diagram showing an example of a peak X appearing in a diffraction pattern obtained from X-ray diffraction measurement using CuKα rays of a solid electrolyte (I). Figure 2 In the X-ray diffraction pattern shown, the intensity of the peak top shows a specific peak with an intensity of 1. In the intensity measurement method, as Figure 2As shown, the average intensity (Av1) in the range of +0.45° to +0.55° is calculated from the diffraction angle 2θ of the peak top of the peak X, and the average intensity (Av2) in the range of -0.55° to -0.45° is calculated from the diffraction angle 2θ of the peak top of the peak X. Next, the arithmetic mean of Av1 and Av2 is calculated, and the ratio of intensity 1 to the arithmetic mean is obtained as the intensity ratio. When the above-mentioned X-ray diffraction characteristics are met, it means that there is no crystal structure or almost no crystal structure in the solid electrolyte (I) and it is in an amorphous state.

[0077] That is, the 1st peak to the 4th peak mentioned above are peaks mainly derived from the crystal structure (for example, the crystal structure of lithium tetraborate) in the solid electrolyte, and the absence of these peaks means that it is in an amorphous state. And, even in the case where there is at least one peak in the 1st peak to the 4th peak, the intensity ratio of at least one peak in the peak X that exists is 5.0 or less, which means that in the solid electrolyte (I), there is almost no crystal structure that hinders the effect of the present invention. In addition, for example, the peak derived from a specific component (for example, a lithium salt) sometimes overlaps with any one of the 1st peak to the 4th peak mentioned above. However, in a solid electrolyte in an amorphous state, the 1st peak to the 4th peak usually decreases, so even if it is assumed that the peak caused by the above-mentioned specific component coincidentally overlaps with any one of the 1st peak to the 4th peak to appear a large peak, there is at least one peak X with an intensity ratio below a specified value, which can be said to indicate that the solid electrolyte (I) is in an amorphous state.

[0078] The above X-ray diffraction measurement was performed using CuKα rays and under the measurement conditions of 0.01° / step, 3° / minute.

[0079] In the X-ray diffraction pattern of the solid electrolyte (I) obtained from the X-ray diffraction measurement using CuKα rays, even if none of the above-mentioned first peak, second peak, third peak and fourth peak exists, or at least one peak X among the above-mentioned first peak, second peak, third peak and fourth peak exists, it is preferred that the intensity ratio of at least one peak X is 3.0 or less.

[0080] Among them, even if the above-mentioned first peak, second peak, third peak and fourth peak do not exist, or at least one peak X among the above-mentioned first peak, second peak, third peak and fourth peak exists, it is preferred that the intensity ratio of at least one peak X is less than 2.0.

[0081] In addition, in the above-mentioned X-ray diffraction spectrum, when there are two or more peaks with peak tops in the range of 21.6 to 22.0° and a half-width of 0.65° or less, the peak with the largest diffraction X-ray intensity is selected as the first peak to determine the above-mentioned X-ray diffraction characteristics.

[0082] Furthermore, in the above-mentioned X-ray diffraction pattern, when there are two or more peaks with peak tops in the range of 25.4 to 25.8° and a full width at half maximum of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the second peak to perform the above-mentioned X-ray diffraction characteristics.

[0083] Furthermore, in the above-mentioned X-ray diffraction spectrum, when there are two or more peaks with peak tops in the range of 33.4 to 33.8° and a half-width of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the third peak to determine the above-mentioned X-ray diffraction characteristics.

[0084] Furthermore, in the above-mentioned X-ray diffraction spectrum, when there are two or more peaks with peak tops in the range of 34.4 to 34.8° and a half-width of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the fourth peak to determine the above-mentioned X-ray diffraction characteristics.

[0085] (Total X-ray Scattering Properties)

[0086] The solid electrolyte (I) preferably satisfies the following requirement A-1 as the total X-ray scattering property. Furthermore, when the solid electrolyte (I) satisfies the above-mentioned X-ray diffraction property, the solid electrolyte (I) usually satisfies the following requirement A-2.

[0087] - Requirement A-1-

[0088] In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (I), there is a peak located at r The first peak and the peak top in the range of r are The second peak in the range of , the peak G(r) of the first peak shows more than 1.0, and the peak G(r) of the second peak shows more than 0.8.

[0089] - Requirement A-2-

[0090] In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (I), when r is greater than and The absolute value of G(r) in the following range is less than 1.0.

[0091] When the solid electrolyte (I) satisfies requirements A-1 and A-2, it has a short-range ordered structure related to the interatomic distance of BO and BB, but has almost no long-range ordered structure, so the oxide solid electrolyte itself shows elastic properties that are softer and more susceptible to plastic deformation than conventional lithium-containing oxides. As a result, it is speculated that in the layer containing the solid electrolyte (I) formed by pressure treatment, the adhesion between the solid electrolytes (I) and / or the adhesion between the solid electrolyte (I) and other components present in the structural layer such as the solid electrolyte layer is improved, and the interface resistance can be reduced, thereby obtaining more excellent ion conductivity.

[0092] The requirements A-1 and A-2 will be described in more detail with reference to the drawings.

[0093] Figure 3 An example of the reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of the solid electrolyte (I) is shown. Figure 3 The vertical axis is the reduced two-body distribution function obtained by Fourier transform of X-ray scattering, which represents the probability of the existence of an atom at a distance r. The total X-ray scattering measurement can be performed by SPring-8BL04B2 (acceleration voltage 61.4keV, wavelength ) is performed. The scattering intensity I obtained by the experiment obs The transformation is performed according to the following steps to obtain the reduced two-body distribution function G(r).

[0094] First, the scattering intensity I obs It is represented by the following formula (1). And, as shown in the following formula (2), the structure factor S(Q) is obtained by dividing the coherent scattering I coh It is obtained by dividing by the product of the number of atoms N and the square of the atomic scattering factor f.

[0095] I obs =I coh +I incoh +I 荧光 (1)

[0096] [Formula 1]

[0097]

[0098] The structure factor S(Q) is used in PDF (Pair Distribution Function) analysis. In the above equation (2), the required intensity is only the coherent scattering I coh . Incoherent scattering I incoh and Fluorescent X-ray I 荧光 can be used to subtract the theoretical formula using a blank measurement and the detector's discriminator from the scattered intensity Iobs Minus.

[0099] Coherent Scattering I coh It is expressed by Debye's scattering formula (the following formula (3)) (N: total number of atoms, f: atomic scattering factor, r ij : the interatomic distance between ij).

[0100] [Formula 2]

[0101]

[0102] If we focus on any atom and let the atomic density at a distance r be ρ(r), then the number of atoms existing in a sphere with a radius of r-r+d(r) is 4πr. 2 ρ(r)dr, the above formula (3) is expressed by the following formula (4).

[0103] [Formula 3]

[0104]

[0105] If the average density of atoms is set to ρ0 and the above formula (4) is modified, the following formula (5) can be obtained.

[0106] [Formula 4]

[0107]

[0108] The following formula (6) can be obtained from the above formula (5) and formula (2).

[0109] [Formula 5]

[0110]

[0111] The two-body distribution function g(r) is expressed by the following equation (7).

[0112] [Formula 6]

[0113]

[0114] The following formula (8) can be obtained from the above formula (6) and formula (7).

[0115] [Formula 7]

[0116]

[0117] As described above, the two-body distribution function can be obtained by Fourier transforming the structure factor S(Q). In order to easily observe the medium-range order / long-range order, the two-body distribution function g(r) is converted into the function of the formula: G(r) = 4πr(g(r)-1) to reduce the two-body distribution function G(r) ( Figure 3 ). g(r) oscillating around 0 represents the density difference from the average density at each interatomic distance, and when there is a correlation at a specific interatomic distance, the average density becomes higher than 1. Therefore, the distance and coordination number of the element corresponding to the local to the intermediate distance are reflected. If the order disappears, ρ(r) approaches the average density, so g(r) gradually approaches 1. Therefore, in an amorphous structure, since the larger r becomes, the more the order disappears, g(r) becomes 1, that is, G(r) becomes 0.

[0118] In Element A-1, if Figure 3 As shown, in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (I), there is a peak located at r The first peak P1 and the peak top are located at r within the range of The second peak P2 is within the range of , the peak G(r) of the first peak P1 shows more than 1.0 (preferably more than 1.2), and the peak G(r) of the second peak P2 shows more than 0.8 (preferably more than 1.0).

[0119] In addition, Figure 3 The peak of the first peak P1 is located at The peak of the second peak P2 is located at

[0120] exist There is a peak at the position of B (boron)-O (oxygen) interatomic distance. There is a peak of the interatomic distance attributed to B (boron)-B (boron) at the position. That is, the observation of the above two peaks (the first peak and the second peak) means that a periodic structure corresponding to the above two interatomic distances exists in the solid electrolyte (I).

[0121] Furthermore, in Element A-2, if Figure 3 As shown, when r is more than and In the following range, the absolute value of G(r) is less than 1.0. As mentioned above, when r is greater than and When the absolute value of G(r) in the following range is less than 1.0, it means that there is almost no long-range ordered structure in the solid electrolyte (I).

[0122] In addition, in the above-mentioned reduced two-body distribution function G(r), when r is In the following range, there are peaks other than the first peak and other than the second peak.

[0123] The method for making the solid electrolyte (I) into an amorphous state is not particularly limited. For example, there is the following method: in the preparation of the solid electrolyte (I), a lithium-containing oxide subjected to mechanical grinding is used as a raw material of the lithium-containing oxide. The mechanical grinding treatment can also be performed in the presence of a lithium salt.

[0124] -Mechanical grinding process-

[0125] Mechanical grinding treatment refers to a process of pulverizing a sample while imparting mechanical energy to the sample. As a mechanical grinding treatment, for example, grinding treatment using a ball mill, a vibration mill, a turbine mill or a disc mill can be cited. From the viewpoint of obtaining amorphous solid electrolyte (I) with good productivity, grinding treatment using a ball mill is preferred. As a ball mill, for example, a vibration ball mill, a rotary ball mill and a planetary ball mill can be cited, and a planetary ball mill is more preferred.

[0126] The conditions of the grinding process using a ball mill (hereinafter referred to as ball milling process) can be appropriately adjusted according to the treatment object. The material of the grinding ball (medium) is not particularly limited, for example, agate, silicon nitride, zirconium oxide, aluminum oxide and iron alloys can be mentioned, preferably yttria stabilized zirconia (YSZ). The average particle size of the grinding ball is not particularly limited. From the perspective of being able to manufacture the solid electrolyte (I) with good productivity, it is preferably 1 to 10 mm, and more preferably 3 to 7 mm. The above average particle size is the value obtained by randomly measuring the diameters of 50 grinding balls and arithmetically averaging them. In the case where the grinding ball is not spherical, the major diameter is set as the diameter. The number of grinding balls is not particularly limited.

[0127] The material of the pulverizing pot in the ball milling treatment is not particularly limited, and examples thereof include agate, silicon nitride, zirconium oxide, aluminum oxide, and iron-based alloys, and yttria-stabilized zirconia (YSZ) is preferred.

[0128] The rotation speed of the ball milling treatment is not particularly limited, for example, it can be set to 200 to 700 rpm, preferably 350 to 550 rpm. The treatment time of the ball milling treatment is not particularly limited, for example, it can be set to 10 to 200 hours, preferably 20 to 140 hours. The atmosphere of the ball milling treatment can be the atmosphere or the atmosphere of an inert gas (for example, argon, helium, nitrogen, etc.).

[0129] As a method for producing a solid electrolyte (I) using a lithium-containing oxide subjected to a mechanical milling treatment, it is preferable to perform the following steps 1A to 3A.

[0130] Step 1A: A step of mechanically grinding a lithium-containing oxide in the presence of a lithium salt

[0131] Step 2A: Step of mixing the product obtained in step 1A with water

[0132] Step 3A: A step of removing water from the dispersion obtained in step 2A to obtain a solid electrolyte (I)

[0133] In step 1A, the amount of the lithium salt used is not particularly limited and can be appropriately adjusted to obtain the solid electrolyte (I) specified in the present invention.

[0134] In the above step 2A, the amount of water used is not particularly limited. For example, the amount of water used can be 10 to 200 parts by mass, preferably 50 to 150 parts by mass, based on 100 parts by mass of the product obtained in step 1A.

[0135] The method of mixing the product obtained in step 1A and water is not particularly limited, and they can be mixed together or water can be added to the product obtained in step 1A in stages for mixing. During mixing, ultrasonic treatment can be performed as needed. The time of ultrasonic treatment is not particularly limited, and can be set to 10 minutes to 5 hours, for example.

[0136] Step 3A is a step of removing water from the dispersion obtained in step 2A to obtain solid electrolyte (I). The method for removing water from the dispersion obtained in step 2A is not particularly limited, and water can be removed by heating treatment or vacuum drying treatment.

[0137] The drying conditions are not particularly limited, and for example, the usual drying conditions used in the usual drying treatment can be appropriately applied, for example, the drying conditions used in the examples can be cited. As usual drying conditions, for example, the following conditions can be cited: natural drying (<30% RH), drying in a desiccator (<5% RH), heating to 100° C. and drying for 30 minutes to 2 hours.

[0138] Prior to the step 1A, a step 0 of subjecting the lithium-containing oxide to mechanical milling in an environment without the presence of a lithium salt may be performed.

[0139] As a method for producing the solid electrolyte (I), it is also preferable to carry out the following steps 1B to 3B instead of the above steps 1A to 3A.

[0140] Step 1B: Mechanical grinding of lithium-containing oxide

[0141] Step 2B: Step of mixing the product obtained in step 1B, water and lithium salt

[0142] Step 3B: A step of removing water from the dispersion obtained in step 2B to obtain a solid electrolyte (I)

[0143] The method of performing steps 1B to 3B is different from the method of performing steps 1A to 3A in that a lithium salt is mixed with the lithium-containing oxide subjected to mechanical milling in the presence of water. Therefore, the difference between step 1B and step 1A is that, in step 1A, mechanical milling is performed in the presence of a lithium salt, whereas in step 1B, mechanical milling is performed without using a lithium salt. Therefore, in step 2B, the product obtained in step 1B, water, and a lithium salt are mixed.

[0144] The steps of step 2B are not particularly limited, and may be a method of mixing the product obtained in step 1B, water, and a lithium salt all together (method 1), a method of mixing the product obtained in step 1B and water to prepare a dispersion, and then mixing the obtained dispersion with a lithium salt (method 2), or a method of mixing the product obtained in step 1B and water to prepare a dispersion 1, mixing a lithium salt and water to prepare a solution 2, and then mixing the dispersion 1 and the solution 2 (method 3). When mixing the product obtained in step 1B and water, a dispersion treatment such as an ultrasonic treatment may be appropriately performed.

[0145] In method 2, when the dispersion obtained by mixing the product obtained in step 1B and water and the lithium salt are mixed, if there is too much lithium salt, the obtained liquid is easily gelled, and the mixing amount of the lithium salt is limited. In contrast, in method 3, even if the product obtained in step 1B and the lithium salt are mixed in approximately equimolar amounts, the liquid is not easily gelled, and the mixing amount of the lithium salt can be further increased. From this point of view, method 3 is preferred.

[0146] Step 3B is the same as step 3A.

[0147] As a method for producing the solid electrolyte (I), it is also preferable to carry out the following steps 1C to 3C instead of the above steps 1A to 3A.

[0148] Step 1C: Step of mechanically grinding the lithium-containing oxide

[0149] Step 2C: Step of mixing the product obtained in step 1C with water

[0150] Step 3C: A step of mixing a product obtained by removing water from the dispersion obtained in step 2C with a lithium salt to obtain a solid electrolyte (I)

[0151] Step 1C is the same as step 1B.

[0152] Step 2C is the same as step 2A.

[0153] Step 3C is different from Steps 3A and 3B in that a product obtained by removing water from the dispersion obtained in Step 2C and a lithium salt are mixed.

[0154] In step 3C, the amount of the lithium salt used is not particularly limited and can be appropriately adjusted to obtain the solid electrolyte (I) specified in the present invention.

[0155] The method of mixing the product obtained by removing water from the dispersion obtained in step 2C and the lithium salt is not particularly limited, and may be a method of immersing a solution obtained by dissolving the lithium salt in water in the product and mixing the two.

[0156] (Component composition of solid electrolyte (I))

[0157] As described above, the solid electrolyte (I) used in the present invention is an amorphous solid electrolyte, in which the ratio of the lithium salt content to the lithium oxide content is 0.001 to 1.5 in molar ratio, and the ratio of the water content to the lithium oxide content is 1 to 12 in molar ratio.

[0158] The ratio of the content of the lithium salt in the solid electrolyte (I) to the content of the lithium-containing oxide is preferably 0.001 to 1.2, more preferably 0.01 to 1.2, further preferably 0.1 to 1.2, and particularly preferably 0.5 to 1.2 in terms of molar ratio.

[0159] Furthermore, the molar ratio of the water content in the solid electrolyte (I) to the lithium-containing oxide content is more preferably 2 to 12, and more preferably 3 to 11. Furthermore, the molar ratio is also preferably 2 to 10, 2 to 8, 2 to 7, and 3 to 7.

[0160] The molar amount of lithium-containing oxide, lithium salt and water in the solid electrolyte (I) can be determined by elemental analysis. As elemental analysis, for example, the elemental analysis method described in the elemental composition of the solid electrolyte (I) described later can be cited. In addition, the molar amount of water can also be determined by the Karl Fischer method, etc.

[0161] The water content in the solid electrolyte (I) is preferably 50% by mass or less, more preferably 45% by mass or less, further preferably 40% by mass or less, and particularly preferably 35% by mass or less. In addition, the water content in the solid electrolyte (I) is also preferably 30% by mass or less, and also preferably 25% by mass or less.

[0162] And, the content of water in the solid electrolyte (I) is usually 5% by mass or more, preferably 10% by mass or more, and preferably 15% by mass or more. Therefore, the content of water in the solid electrolyte (I) is preferably 5 to 50% by mass, more preferably 5 to 45% by mass, further preferably 10 to 40% by mass, particularly preferably 10 to 35% by mass, also preferably 10 to 30% by mass, also preferably 15 to 30% by mass, and also preferably 15 to 25% by mass.

[0163] The content of the lithium-containing oxide in the solid electrolyte (I) is preferably 20 to 80% by mass, more preferably 20 to 75% by mass, and still more preferably 25 to 70% by mass.

[0164] The content of the lithium salt in the solid electrolyte (I) is preferably 0.5 to 60% by mass, more preferably 1.0 to 55% by mass, further preferably 2.0 to 50% by mass, and still more preferably 5.0 to 50% by mass.

[0165] -Contains lithium oxide-

[0166] As described above, the lithium-containing oxide constituting the solid electrolyte (I) contains Li, B, and O.

[0167] The lithium-containing oxide is preferably composed of Li 2+x B 4+y O 7+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). That is, when the molar amount of B is set to 4.00 to represent the molar amount of Li, the molar amount of Li is preferably 1.58 to 2.49 (i.e., 1.7×4 / 4.3 to 2.3×4 / 3.7), and the molar amount of O is 6.23 to 7.89 (i.e., 6.7×4 / 4.3 to 7.3×4 / 3.7). In other words, when the molar content of B is set to 4.00, the relative value of the molar content of Li is preferably 1.58 to 2.49, and the molar amount of O is 6.23 to 7.89. As such a lithium-containing oxide, typically lithium tetraborate (Li2B4O7) can be cited.

[0168] Furthermore, the lithium-containing oxide is preferably composed of Li 1+x B 3+y O 5+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). Such lithium-containing oxides typically include lithium triborate (LiB3O5).

[0169] Furthermore, the lithium-containing oxide is preferably composed of Li 3+x B 11+y O 18+z(-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3) is a compound represented by (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). As such lithium-containing oxides, Li3B 11 O 18 .

[0170] Furthermore, the lithium-containing oxide is preferably composed of Li 3+x B 7+y O 12+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). As such lithium-containing oxides, Li3B7O is typically mentioned. 12 .

[0171] Therefore, the lithium-containing oxide is preferably the Li 2+x B 4+y O 7+z , the above Li 1+x B 3+y O 5+z , Li 3+x B 11+y O 18+z Li 3+x B 7+y O 12+z At least one of the following.

[0172] Furthermore, LiBO5, Li2B7O 12 , LiB2O3(OH)H2O and Li4B8O 13 At least one of (OH)2(H2O)3 and the like is used as the lithium-containing oxide.

[0173] In the solid electrolyte (I), the lithium-containing oxide is preferably in an amorphous state. That is, the lithium-containing oxide in the solid electrolyte (I) is preferably also in a desired amorphous state so that the solid electrolyte (I) is in the above-mentioned amorphous state.

[0174] Among them, the lithium-containing oxide is preferably lithium tetraborate in an amorphous state.

[0175] -Lithium salts-

[0176] The lithium salt constituting the solid electrolyte (I) used in the present invention is not particularly limited, and examples thereof include Li + and anions, preferably Li + and an organic anion, more preferably a salt composed of Li + And salts composed of organic anions having halogen atoms.

[0177] The lithium salt constituting the solid electrolyte (I) used in the present invention preferably contains two or more specific elements selected from the group consisting of elements of Group 3 of the periodic table, elements of Group 4 of the periodic table, elements of Group 13 of the periodic table, elements of Group 14 of the periodic table, elements of Group 15 of the periodic table, elements of Group 16 of the periodic table, elements of Group 17 of the periodic table and H.

[0178] As the lithium salt constituting the solid electrolyte (I) used in the present invention, for example, a compound represented by the following formula (1) is preferable.

[0179] Formula (1) LiN(R f1 SO2)(R f2 SO2)

[0180] R f1 and R f2 R each independently represents a halogen atom or a perfluoroalkyl group. f1 and R f2 They can be the same as each other or different from each other.

[0181] R f1 and R f2 In the case of a perfluoroalkyl group, the number of carbon atoms in the perfluoroalkyl group is not particularly limited.

[0182] R f1 and R f2 It is preferably a halogen atom or a perfluoroalkyl group having 1 to 6 carbon atoms, more preferably a halogen atom or a perfluoroalkyl group having 1 to 2 carbon atoms, and still more preferably a halogen atom. If the volume of the terminal group increases, the steric hindrance increases, which becomes a factor that hinders ion conduction. Therefore, R f1 and R f2 In the case of a perfluoroalkyl group, the one having a smaller number of carbon atoms is preferred.

[0183] The lithium salt that can be contained in the solid electrolyte (I) used in the present invention is not limited to the compound represented by the above formula (1). The lithium salt that can be contained in the solid electrolyte (I) used in the present invention is exemplified below.

[0184] (L-1) Inorganic lithium salts: inorganic fluoride salts such as LiPF6, LiBF4, LiAsF6 and LiSbF6; perhalide salts such as LiClO4, LiBrO4 and LiIO4; inorganic chloride salts such as LiAlCl4.

[0185] (L-2) Fluorine-containing organic lithium salt:

[0186] Perfluoroalkyl sulfonates such as LiCF3SO3; fluorosulfonyl imide salts or perfluoroalkyl sulfonyl imide salts such as LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(FSO2)2 (also recorded as Li(FSO2)2N in this specification) and LiN(CF3SO2)(C4F9SO2); perfluoroalkyl sulfonyl methyl salts such as LiC(CF3SO2)3; fluoroalkyl fluorophosphates (preferably perfluoroalkyl fluorophosphates) such as Li[PF5(CF2CF2CF3)], Li[PF4(CF2CF2CF3)2], Li[PF3(CF2CF2CF3)3], Li[PF5(CF2CF2CF2CF3)], Li[PF4(CF2CF2CF2CF3)2] and Li[PF3(CF2CF2CF2CF3)3].

[0187] (L-3) Oxalate borate: lithium bis(oxalato)borate and lithium difluorooxalatoborate.

[0188] In addition to the above, examples of lithium salts include LiF, LiCl, LiBr, Li I, Li2SO4, LiNO3, Li2CO3, CH3COOLi, LiAsF6, LiSbF6, LiAlCl4 and LiB(C6H5)4.

[0189] Among them, LiPF6, LiBF4, LiAsF6, LiSbF6, LiClO4, Li(R f11 SO2)、LiN(R f11 SO2)2, LiN(FSO2)2 or LiN(R f11 SO2)(R f12 SO2), more preferably LiPF6, LiBF4, LiN(R f11 SO2)2, LiN(FSO2)2 or LiN(R f11 SO2)(R f12 SO2). In these examples, R f11 and R f12 Each independently represents a perfluoroalkyl group, and the number of carbon atoms is preferably 1 to 6, more preferably 1 to 4, and even more preferably 1 to 2. f11 and R f12 They may be the same or different from each other. Furthermore, LiNO3 and 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonylimide lithium are also preferred as the lithium salt.

[0190] (Elemental composition of solid electrolyte (I))

[0191] Regarding the solid electrolyte (I), the composition of the components is described based on the compound constituting the solid electrolyte (I). Next, the solid electrolyte (I) is described from the perspective of the preferred elemental composition. That is, in one embodiment of the secondary battery of the present invention, regarding the solid electrolyte (I), having "lithium-containing oxide" and "lithium salt" is not considered as a specific invention matter, but can be determined by the elemental composition, for example, as follows.

[0192] When the molar amount of B in the solid electrolyte (I) is set to 4.00, the molar amount of Li in the solid electrolyte (I) used in the present invention is preferably 1.58 to 3.49 (preferably 1.58 to 3.00, more preferably 1.90 to 3.00, and further preferably 2.00 to 3.00). Furthermore, when the molar amount of B in the solid electrolyte (I) is set to 4.00, the molar amount of O is preferably 6.23 to 25.00 (preferably 6.50 to 23.00, more preferably 8.00 to 23.00, further preferably 10.00 to 23.00, and particularly preferably 10.00 to 18.00). Furthermore, when the molar amount of B in the solid electrolyte (I) is set to 4.00, the molar amounts of elements other than B, other than Li, and other than O are preferably 0.001 to 10.00 (preferably 0.001 to 6.00, and further preferably 0.01 to 5.00), respectively.

[0193] The content of each element is determined by conventional elemental analysis. As a method of elemental analysis, for example, Li and B are analyzed by ICP-OES (Inductively coupled plasma optical emission spectrometry), N and the like are analyzed by an inert gas fusion method, and for example, F and S are analyzed by combustion ion chromatography. For O, the analysis masses of elements other than O can be added and calculated as a difference from the total amount of powder. In addition, the method for calculating the content of each element is not limited to the above. Taking into account the structure of the compound used, the content of other elements can be estimated based on the analysis results of the content of one element.

[0194] Based on the content of each element calculated by elemental analysis, the molar amounts of Li, O, and other elements when the molar amount of B is set to 4.00 were calculated.

[0195] In a preferred embodiment of the solid electrolyte (I), in addition to Li, B and O, the solid electrolyte (I) also contains one or more elements (E) selected from the group consisting of elements of Group 4 of the periodic table, elements of Group 15 of the periodic table, elements of Group 16 of the periodic table, elements of Group 17 of the periodic table, Si, C, Sc and Y, and more preferably contains two or more elements.

[0196] Examples of the Group 4 elements of the periodic table include Ti, Zr, Hf and Rf. Examples of the Group 15 elements of the periodic table include N, P, As, Sb, Bi and Mc. Examples of the Group 16 elements of the periodic table include S, Se, Te, Po and Lv. Examples of the Group 17 elements of the periodic table include F, Cl, Br, I, At and Ts.

[0197] Among them, it is preferred that the element (E) contains one or more elements selected from F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N, and it is more preferred that the element (E) contains two or more elements selected from F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N.

[0198] The number of the element (E) contained in the solid electrolyte (I) may be 3 or more, preferably 2 to 5, and more preferably 2 to 4.

[0199] As a preferred embodiment of the solid electrolyte (I), it is preferred to contain two or more elements (E) selected from F, S, N, P and C, more preferably to contain two or more elements (E) selected from F, S, C and N, and further preferably to contain three elements (E) of F, S and N.

[0200] In the solid electrolyte (I) containing one or more (preferably two or more) of the above-mentioned element (E), when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of Li, the molar amount of Li is preferably 1.58 to 3.49. That is, when the molar content of B is set to 4.00, the relative value of the molar content of Li is preferably 1.58 to 3.49. Among them, when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of Li, the molar amount of Li is preferably 1.58 to 3.00, more preferably 1.90 to 3.00, and further preferably 2.00 to 3.00.

[0201] In the solid electrolyte (I) containing one or more (preferably two or more) of the above-mentioned element (E), when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of O, the molar amount of O is preferably 6.23 to 25.00. That is, when the molar content of B is set to 4.00, the relative value of the molar content of O is preferably 6.23 to 25.00. Among them, when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of O, the molar amount of O is preferably 6.50 to 23.00, more preferably 8.00 to 23.00, more preferably 10.00 to 23.00, and particularly preferably 10.00 to 18.00.

[0202] In a solid electrolyte (I) containing one or more (preferably two or more) of the above-mentioned element (E), when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of the element (E), the molar amount of each element (E) is preferably 0.001 to 10.00. That is, when the molar content of B is set to 4.00, the relative value of the molar content of each element (E) is preferably 0.001 to 10.00. Among them, when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of the element (E), the molar amount of each element (E) is preferably 0.001 to 6.00, and more preferably 0.01 to 5.00.

[0203] As one of the preferred aspects of the elemental composition of the solid electrolyte (I) containing one or more (preferably two or more) of the above-mentioned element (E), it can be mentioned that when Li, B, O, F, S and N are contained and the molar amount of B is 4.00, the molar amount of Li is 1.58 to 3.49 (preferably 1.58 to 3.00, more preferably 1.90 to 3.00, and further preferably 2.00 to 3.00), the molar amount of O is 6.23 to 25.00 (preferably The molar amount of F is 0.001-10.00 (preferably 0.01-10.00), the molar amount of S is 0.001-2.00 (preferably 0.01-2.00), and the molar amount of N is 0.001-1.00 (preferably 0.005-1.00) of the solid electrolyte.

[0204] The solid electrolyte (I) used in the present invention is the above-mentioned amorphous solid electrolyte. As a result, it is preferred that the solid electrolyte (I) exhibits the following characteristics in addition to the above-mentioned X-ray diffraction characteristics.

[0205] (Solid State 7 Li-NMR spectral characteristics)

[0206] Regarding the solid electrolyte (I), the solid electrolyte (I) was solidified at 20°C and 120°C. 7 The full width at half maximum ratio calculated from the spectrum obtained by Li-NMR measurement by the method described below is preferably 50% or less, more preferably 40% or less, and further preferably 35% or less. The lower limit is not particularly limited, but is often 10% or more.

[0207] The above-mentioned half-peak full width ratio is obtained by the following calculation: The solid electrolyte (I) is solidified at 20°C and 120°C respectively. 7Li-NMR measurement, and after obtaining the half-maximum full width (half-maximum full width 1) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained in the measurement at 20°C and the half-maximum full width (half-maximum full width 2) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained in the measurement at 120°C, the percentage of the ratio of the half-maximum full width 2 to the half-maximum full width 1 is calculated {(half-maximum full width 2 / half-maximum full width 1) × 100 (%)}. The half-maximum full width (FWHM) of the peak refers to the width (ppm) at the 1 / 2 point (H / 2) of the height (H) of the peak.

[0208] Below, use Figure 4 The above characteristics are explained. Figure 4 In the figure, the solid electrolyte (I) is prepared at 20°C or 120°C. 7 An example of a spectrum obtained during Li-NMR measurement. Figure 4 The solid line spectrum shown on the lower side is the solid state spectrum at 20°C. 7 The spectrum obtained during Li-NMR measurement is Figure 4 The dotted spectrum shown on the upper side is a spectrum obtained by solid-state heating at 120°C. 7 Spectra obtained during Li-NMR measurement.

[0209] Generally speaking, in solid 7 In Li-NMR measurement, Li + In case of high mobility, the peak obtained is sharper. Figure 4 In the manner shown, when comparing the spectrum at 20°C with the spectrum at 120°C, the spectrum at 120°C becomes sharper. Figure 4 In the embodiment shown, it is shown that Li + It is believed that the solid electrolyte (I) is prone to plastic deformation due to the defective structure as described above, and Li + Excellent jumping performance.

[0210] For reference, regarding ordinary lithium tetraborate crystals, solid-state 7 During Li-NMR measurement, Figure 5 The spectrum measured at 20°C is shown by the solid line at the bottom of Figure 5 The spectra measured at 120° C. indicated by the dotted line shown above tend to have substantially the same shape. That is, in the lithium tetraborate crystal, there are no Li defects or the like, and as a result, the elastic modulus is high and plastic deformation is not easily caused.

[0211] The above solid 7Li-NMR measurement conditions are as follows.

[0212] The measurement was performed using a 4 mm HX CP-MAS probe by a single pulse method with a 90° pulse width of 3.2 μs, an observation frequency of 155.546 MHz, an observation width of 1397.6 ppm, a repetition time of 15 seconds, a cumulative integration of 1 time, and a MAS rotation speed of 0 Hz.

[0213] Furthermore, the solid electrolyte (I) used in the present invention is preferably as follows: 7 When the first peak appearing in the range of -100 to +100 ppm in the spectrum obtained during Li-NMR measurement is subjected to waveform separation, there is a second peak having a chemical shift in the range of -3 to +3 ppm and a half-maximum width of less than 5 ppm, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 0.5% or more. The ratio of the above-mentioned area intensity is more preferably 2% or more, further preferably 5% or more, particularly preferably 10% or more, and most preferably 15% or more. In the embodiment of the present invention wherein the solid electrolyte (I) contains water, the solid electrolyte (I) 7 The Li-NMR spectrum characteristics tend to be as described above. The upper limit of the ratio of the area intensity is not particularly limited, but is often 50% or less.

[0214] Below, use Figure 6 and Figure 7 The above characteristics are described.

[0215] exist Figure 6 The solid electrolyte (I) is shown in FIG. 7 An example of a spectrum obtained during Li-NMR measurement. Figure 6 As shown, a peak (corresponding to the first peak) is observed in the solid electrolyte (I) in the range of -100 to +100 ppm, and in the first peak, a small peak surrounded by a dotted line is observed near the chemical shift of 0 ppm. + When the mobility is high, a sharp peak can be observed, thus producing its influence.

[0216] Then, in Figure 7 , a diagram showing the separation of the first peak waveform is shown. Figure 7 As shown, the first peak is separated into a small peak (corresponding to the second peak) represented by a solid line and a large peak represented by a dotted line. The second peak is a peak with a chemical shift in the range of -3 to +3 ppm and a full width at half maximum of less than 5 ppm.

[0217] The solid electrolyte (I) is preferably composed of Figure 7The solid line represents the area intensity of the second peak relative to that of Figure 6 The ratio of the area intensity of the first peak (the peak before the waveform separation) {(area intensity of the second peak / area intensity of the first peak)×100(%)} is within the above range.

[0218] As a method of waveform separation, a method using known software can be mentioned. As software, for example, Igor Pro, a graphics processing software of WaveMetrics, Inc. can be mentioned.

[0219] (Raman spectroscopy characteristics)

[0220] Regarding the solid electrolyte (I), in the Raman spectrum of the solid electrolyte (I), 600 to 850 cm -1 In the wave number region, the coefficient of determination obtained by linear regression analysis by the least square method is preferably 0.9400 or more, more preferably 0.9600 or more, and also preferably 0.9800 or more. The upper limit is not particularly limited, but is usually 1.0000 or less.

[0221] refer to Figure 8 , the above Raman spectral characteristics are explained.

[0222] First, a Raman spectrum of the solid electrolyte (I) is obtained. As a method for measuring Raman spectra, Raman imaging is implemented. Raman imaging refers to microscopic spectroscopy combined with microscopy in Raman spectroscopy. Specifically, it is a method of detecting measurement light containing Raman scattered light by scanning excitation light on a sample, and visualizing the distribution of components based on the intensity of the measurement light.

[0223] The measurement conditions of Raman imaging are as follows: 27°C and in the atmosphere, excitation light of 532nm, objective lens of 100 times, point scanning in mapping mode, 1μm step length, exposure time of 1 second per point, accumulation and integration times of 1 time, and measurement range of 70μm×50μm. However, the measurement range may become narrower depending on the film thickness of the sample.

[0224] Furthermore, the Raman spectrum data is subjected to principal component analysis (PCA) processing to remove noise. Specifically, in the principal component analysis processing, the spectrum is reorganized using components having an autocorrelation coefficient of 0.6 or more.

[0225] exist Figure 8 An example of the Raman spectrum of the solid electrolyte (I) is shown in FIG. Figure 8 In the graph shown, the vertical axis represents the Raman intensity and the horizontal axis represents the Raman shift. Figure 8 The Raman spectrum shown is from 600 to 850 cm -1The coefficient of determination (R 2 ). That is, in Figure 8 The Raman spectrum of 600-850 cm -1 In the wave number region, the regression line is obtained by the least square method ( Figure 8 The bold line in the figure is used to calculate the coefficient of determination R of the regression line. 2 In addition, the coefficient of determination takes a value between 0 (no linear correlation) and 1 (complete linear correlation of the measured values) depending on the linear correlation of the measured values.

[0226] In solid electrolyte (I), such as Figure 8 As shown, at 600-850cm -1 In the wavenumber region, almost no peak is observed, and as a result, a high determination coefficient is shown.

[0227] In addition, the above determination coefficient R 2 It is equivalent to the square of the correlation coefficient (Pearson product-moment correlation coefficient). More specifically, in this specification, the coefficient of determination R 2 The calculation is performed by the following formula: wherein x1 and y1 represent the wave number in the Raman spectrum and the Raman intensity corresponding to the wave number, x2 represents the (arithmetic) average of the wave number, and y2 represents the (arithmetic) average of the Raman intensity.

[0228] [Formula 8]

[0229]

[0230] On the other hand, for reference, Fig. 9 The Raman spectrum of a typical lithium tetraborate crystal is shown in FIG. Fig. 9 As shown, in the case of a conventional lithium tetraborate crystal, the wavelengths of 716 to 726 cm-1 are derived from its structure. -1 and 771~785cm -1 In the wave number region of 600-850 cm -1 In the wave number region, when the coefficient of determination was calculated by linear regression analysis using the least squares method, the coefficient of determination was less than 0.9400.

[0231] That is, when the determination coefficient is 0.9400 or more, it means that the solid electrolyte (I) contains almost no crystal structure. Therefore, as a result, it is considered that the solid electrolyte (I) has the characteristics of being easy to plastically deform and Li + Excellent jumping properties.

[0232] (Infrared absorption spectrum characteristics)

[0233] In the infrared absorption spectrum of solid electrolyte (I), the -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The ratio of the maximum absorption intensity in the wave number region (between 3000 and 3500 cm -1 The maximum absorption intensity in the wave number region of 800 to 1600 cm -1 The maximum absorption intensity in the wave number region of the wavelength region is preferably 1 / 5 or more (0.2 or more). Among them, the above ratio is preferably 3 / 10 or more, more preferably 2 / 5 or more. The upper limit is not particularly limited, but is preferably 1 or less.

[0234] In the infrared absorption spectrum, the range of 3000 to 3500 cm -1 The OH stretching vibration mode is observed in the wave number region of 800-1600 cm -1 The BO stretching vibration mode is observed in the wave number region. In the solid electrolyte (I), a strong absorption intensity originating from the OH stretching vibration mode is observed, which indicates that a large amount of OH groups and / or a large amount of water are contained. In this solid electrolyte (I), lithium ions become easy to move, and as a result, the ion conductivity tends to be improved.

[0235] In addition, at 800-1600cm -1 In the wave number region, vibration modes originating from lithium salts can also be observed.

[0236] The infrared absorption spectrum measurement conditions can be set as follows.

[0237] Objective lens: 32x Cassegrain (NA0.65), Detector: MCT-A, Measuring range: 650~4000cm -1 , Resolution: 4cm -1 , Sample cell: Use diamond cell for measurement.

[0238] The infrared absorption spectrum obtained was corrected to remove signals from water and CO 2 in the atmosphere, and the background was offset corrected so that the absorption intensity became 0. After vacuum drying at 40° C. for 2 hours, the spectrum was measured in the atmosphere.

[0239] The ion conductivity (27°C) of the solid electrolyte (I) is not particularly limited, but is preferably 1.0×10 -5 S / cm or more, more preferably 1.0×10 -4 S / cm or more, more preferably 1.0×10 -3 S / cm or more, particularly preferably 3.0×10 -3S / cm or more. The upper limit is not particularly limited, but is often 1.0×10 -2 S / cm or less.

[0240] Furthermore, the solid electrolyte (I) also preferably exhibits the following characteristics or properties.

[0241] (Mass reduction rate)

[0242] The mass reduction rate of the solid electrolyte (I) when heated to 800°C is preferably 20 to 40% by mass, more preferably 25 to 35% by mass. The mass reduction caused by the above heating is believed to be the removal of water contained in the solid electrolyte (I). By containing such water, the solid electrolyte (I) can further improve the conductivity of lithium ions.

[0243] In the above-mentioned heating treatment, heating is performed at a temperature increase rate of 20°C / second within a range of 25°C to 800°C. When measuring the mass reduction, a known thermogravimetric differential thermal analysis (TG-DTA) device can be used. The above-mentioned mass reduction rate is calculated as follows:

[0244] {(mass at 25°C - mass at 800°C) / mass at 25°C}×100.

[0245] When measuring the mass reduction rate, the solid electrolyte (I) was previously vacuum dried at 40° C. for 2 hours. The mass reduction rate was measured in the atmosphere.

[0246] The solid electrolyte layer constituting the secondary battery of the present invention may contain other components in addition to the solid electrolyte (I).

[0247] For example, the solid electrolyte layer can include a binder composed of an organic polymer. The organic polymer constituting the binder can be in a particle form or a non-particle form. By including the binder, cracks can be more reliably prevented from occurring in the solid electrolyte layer or the electrode layer.

[0248] Furthermore, the solid electrolyte layer may include other solid electrolytes other than the solid electrolyte (I). Other solid electrolytes refer to solid electrolytes that enable lithium ions to move inside them. As solid electrolytes, inorganic solid electrolytes are preferred. As other solid electrolytes, oxide-based solid electrolytes, halide-based solid electrolytes and hydride-based solid electrolytes can be cited, preferably oxide-based solid electrolytes.

[0249] The thickness of the solid electrolyte layer constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 10 to 1000 μm, preferably 50 to 400 μm, or, for example, 0.1 to 50 μm, in which case it is preferably 1 to 20 μm.

[0250] <Positive electrode layer>

[0251] The positive electrode layer is usually composed of a positive electrode collector layer and a positive electrode active material layer, but can also be a structure composed of a positive electrode active material layer and not including a positive electrode collector layer. In other words, when the positive electrode active material layer also functions as a positive electrode collector layer, it is not necessary to be composed of the two layers of the positive electrode collector layer and the positive electrode active material layer, and can be a single-layer structure.

[0252] Furthermore, the positive electrode active material layer generally contains a solid electrolyte (preferably an inorganic solid electrolyte) together with the positive electrode active material, but may not contain a solid electrolyte.

[0253] In the case where the positive electrode active material layer contains a solid electrolyte, the type of the solid electrolyte is not particularly limited. From the viewpoint of achieving both flexibility and safety at a high level, it is preferred to use the above-mentioned solid electrolyte (I). In this way, the solid electrolyte (I) can also act as a binder to the solid particles contained in the positive electrode layer, thereby enabling the positive electrode layer to have higher flexibility.

[0254] The positive electrode active material layer may contain one or more solid electrolytes.

[0255] The content of the solid electrolyte in the positive electrode active material layer is not particularly limited, but is preferably 50 to 99.9% by mass, more preferably 70 to 99.5% by mass, and even more preferably 90 to 99% by mass as the total content with the positive electrode active material.

[0256] The positive electrode active material used in the positive electrode layer itself can be widely used from those that can be used in ordinary lithium ion secondary batteries. Preferred embodiments of the positive electrode active material will be described below.

[0257] (Positive electrode active material)

[0258] The positive electrode active material is preferably a positive electrode active material that can reversibly insert and / or release lithium ions. The positive electrode active material is not particularly limited, preferably a transition metal oxide, more preferably a transition metal oxide containing a transition metal element Ma (one or more elements selected from Co, Ni, Fe, Mn, Cu and V). In addition, the element Mb (metal elements of the 1st (Ia) group of the periodic table other than lithium, elements of the 2nd (IIa) group, Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P and B, etc.) can be mixed in the transition metal oxide. As the mixing amount of the element Mb, it is preferably 0 to 30 mol% relative to the amount of the transition metal element Ma (100 mol%). More preferably, the material synthesized by mixing in a manner such that the molar ratio of Li / Ma is 0.3 to 2.2.

[0259] Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) transition metal phosphate compounds containing lithium, (MD) transition metal halophosphate compounds containing lithium, and (ME) transition metal silicate compounds containing lithium.

[0260] Examples of the transition metal oxide (MA) having a layered rock salt structure include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).

[0261] Examples of the transition metal oxide (MB) having a spinel structure include LiMn2O4 (LMO), LiNi 0.5 Mn 1.5 O4([LNMO]), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8 and Li2NiMn3O8.

[0262] As (MC) transition metal phosphate compounds containing lithium, for example, there can be mentioned olivine-type iron phosphate salts such as LiFePO4 ([LFP]) and Li3Fe2(PO4)3, pyrophosphate iron salts such as LiFeP2O7, cobalt phosphate salts such as LiCoPO4, cobalt pyrophosphate salts such as Li2CoP2O7, and monoclinic NASICON-type vanadium phosphate salts such as Li3V2(PO4)3 (lithium vanadium phosphate).

[0263] Examples of the lithium-containing transition metal halophosphate compound (MD) include iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.

[0264] Examples of the (ME) lithium-containing transition metal silicate compound include Li 2 FeSiO 4 , Li 2 MnSiO 4 , and Li 2 CoSiO 4 .

[0265] The shape of the positive electrode active material is not particularly limited, and is usually in the form of particles. The volume average particle size of the positive electrode active material is not particularly limited, and is preferably 0.1 to 50 μm, for example. The volume average particle size of the positive electrode active material can be determined in the same manner as the volume average particle size of the negative electrode active material described later.

[0266] The positive electrode active material obtained by the calcination method can be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.

[0267] The positive electrode active material may be surface-coated with a surface coating agent, sulfur or phosphorus, which will be described later, in the same manner as the negative electrode active material, which will be described later, or with active light.

[0268] The positive electrode active material may be used alone or in combination of two or more.

[0269] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is preferably 10 to 97% by mass, more preferably 30 to 95% by mass, further preferably 40 to 93% by mass, and particularly preferably 50 to 90% by mass.

[0270] Among these, LiCoO2 (LCO), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM), LiFePO4(LFP), LiMn2O4(LMO), LiNi 0.5 Mn 1.5 O4(LNMO) or Li2CoP2O7 or a material coated with an interface resistance stabilizing layer such as an oxide or carbon-based material described later.

[0271] (Positive electrode current collector layer)

[0272] The current collector layer constituting the positive electrode layer is an electron conductor and is generally in the form of a thin film sheet.

[0273] Examples of the constituent material of the positive electrode current collector layer include aluminum (Al), aluminum alloy (Al alloy), copper (Cu), stainless steel, nickel and titanium. Aluminum, aluminum alloy, copper (Cu) or titanium is preferred, and aluminum, aluminum alloy or copper (Cu) is more preferred.

[0274] In addition, examples of the positive electrode current collector layer include a positive electrode current collector layer having a coating layer (thin film) of carbon, nickel, titanium, aluminum or silver on the surface of aluminum or stainless steel.

[0275] As the Al alloy, for example, Al-Cu alloy (about 500-640°C), Al-Mn alloy (about 640°C), Al-Si alloy (about 530-570°C), Al-Mg alloy (about 570-650°C), Al-Mg-Si alloy (about 580-650°C), Al-Zn-Mg alloy (about 480-640°C) can be cited. In addition, the temperature in the brackets means the melting point at normal pressure.

[0276] The thickness of the positive electrode active material layer constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 5 to 500 μm, preferably 20 to 200 μm, and can also be, for example, 0.1 to 50 μm, and in this case, is preferably 1 to 20 μm.

[0277] The thickness of the positive electrode collector layer constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 10 to 100 μm, preferably 10 to 50 μm, and can also be, for example, 0.01 to 20 μm, in which case it is preferably 0.05 to 10 μm, and more preferably 0.1 to 5 μm.

[0278] <Negative electrode layer>

[0279] The negative electrode layer is usually composed of a negative electrode current collector layer and a negative electrode active material layer, but can also be a structure composed of a negative electrode active material layer and not including a negative electrode current collector layer. In other words, when the negative electrode active material layer also functions as a negative electrode current collector layer, it is not necessary to be composed of the two layers of the negative electrode current collector layer and the negative electrode active material layer, and can be a single-layer structure.

[0280] Furthermore, the negative electrode active material layer generally contains a solid electrolyte (preferably an inorganic solid electrolyte) together with the negative electrode active material, but may not contain a solid electrolyte.

[0281] In the case where the negative electrode active material layer contains a solid electrolyte, the type of the solid electrolyte is not particularly limited. From the viewpoint of achieving both flexibility and safety at a high level, the above-mentioned solid electrolyte (I) is preferably used. In this way, the solid electrolyte (I) can also act as a binder to the solid particles contained in the negative electrode layer, thereby making the negative electrode layer have higher flexibility.

[0282] The negative electrode active material layer may contain one or two or more solid electrolytes.

[0283] The content of the solid electrolyte in the negative electrode active material layer is not particularly limited, but is preferably 50 to 99.9% by mass, more preferably 70 to 99.5% by mass, and even more preferably 90 to 99% by mass as the total content with the negative electrode active material.

[0284] The negative electrode active material used in the negative electrode layer itself can be widely used from those that can be used in ordinary lithium ion secondary batteries. Preferred embodiments of the negative electrode active material will be described below.

[0285] (Negative electrode active material)

[0286] The negative electrode active material is preferably a negative electrode active material that can reversibly insert and release lithium ions. The negative electrode active material is not particularly limited, and examples thereof include carbonaceous materials, oxides of metal elements or semi-metal elements, lithium monomers, lithium alloys, and negative electrode active materials that can form alloys with lithium.

[0287] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon, for example, carbonaceous materials made of various synthetic resins such as calcined petroleum pitch, carbon black such as acetylene black (AB), graphite (natural graphite and artificial graphite such as vapor-grown graphite), and PAN (polyacrylonitrile) resin or furfuryl alcohol resin.

[0288] In addition, various carbon fibers such as PAN-based carbon fibers, cellulose-based carbon fibers, pitch-based carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol)-based carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers, as well as intermediate phase microspheres, graphite whiskers, and flat graphite can also be cited.

[0289] These carbonaceous materials can be further divided into hardly graphitizable carbonaceous materials (also called hard carbon) and graphite-based carbonaceous materials according to the degree of graphitization.

[0290] Furthermore, the carbonaceous material preferably has the interplanar spacing, density or crystallite size described in Japanese Patent Laid-Open No. 62-022066, Japanese Patent Laid-Open No. 2-006856 and Japanese Patent Laid-Open No. 3-045473. The carbonaceous material need not be a single material, and a mixture of natural graphite and artificial graphite described in Japanese Patent Laid-Open No. 5-090844 and graphite with a coating layer described in Japanese Patent Laid-Open No. 6-004516 can also be used.

[0291] As the carbonaceous material, hard carbon or graphite is preferred, and graphite is more preferred.

[0292] The oxide of the metal element or semi-metal element used as the negative electrode active material is not particularly limited as long as it is an oxide that can occlude and release lithium, and examples thereof include oxides of metal elements such as Fe3O4 (metal oxides), composite oxides of metal elements, composite oxides of metal elements and semi-metal elements, and oxides of semi-metal elements (semi-metal oxides). In addition, composite oxides of metal elements and composite oxides of metal elements and semi-metal elements are collectively referred to as metal composite oxides.

[0293] As these oxides, amorphous oxides are preferred, and chalcogenides which are reaction products of metal elements and elements of Group 16 of the periodic table are also preferred.

[0294] In the present invention, semi-metallic elements refer to elements showing properties between metal elements and non-metallic elements, and generally include six elements of boron, silicon, germanium, arsenic, antimony and tellurium, and also include three elements of selenium, polonium and astatine.

[0295] Furthermore, amorphous means that, by X-ray diffraction using CuKα rays, a broad scattering band having a vertex in a region of 20 to 40° in 2θ values ​​may also have crystalline diffraction lines. It is preferred that the strongest intensity of the crystalline diffraction lines seen in a region of 40 to 70° in 2θ values ​​is 100 times or less, more preferably 5 times or less, and further preferably a diffraction line having no crystalline diffraction line intensity at the vertex of the broad scattering band seen in a region of 20 to 40° in 2θ values.

[0296] Among the compound group consisting of the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements or the above-mentioned chalcogenides are more preferred, and (complex) oxides or chalcogenides consisting of a single element or a combination of two or more elements selected from Groups 13 (IIIB) to 15 (VB) of the periodic table (for example, Al, Ga, Si, Sn, Ge, Pb, Sb and Bi) are further preferred.

[0297] As amorphous oxides and chalcogenides, preferred are Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3 or Sb2S5.

[0298] As the negative electrode active material that can be used together with the amorphous oxide negative electrode active material centered on Sn, Si or Ge, carbonaceous materials that can occlude and / or release lithium ions or lithium metal, lithium monomers, lithium alloys, or negative electrode active materials that can alloy with lithium are preferred.

[0299] From the viewpoint of high current density charge and discharge characteristics, the oxide of a metal element or a semi-metal element (particularly a metal (complex) oxide) and the above-mentioned chalcogenide preferably contain at least one of titanium and lithium as a constituent component.

[0300] Examples of the metal composite oxide containing lithium (lithium composite metal oxide) include composite oxides of lithium oxide and the above-mentioned metal oxides, the above-mentioned metal composite oxides or the above-mentioned chalcogenides. More specifically, Li2SnO2 is included.

[0301] The negative electrode active material (e.g., metal oxide) preferably contains titanium element (titanium oxide) as well. Specifically, since the volume change during the occlusion and release of lithium ions is small, the rapid charge and discharge characteristics are excellent. From the viewpoint of being able to improve the life of the all-solid-state lithium ion secondary battery with suppressed electrode deterioration, Li4Ti5O 12 (lithium titanate [LTO]) is preferred.

[0302] Regarding the lithium alloy as the negative electrode active material, there is no particular limitation as long as it is an alloy commonly used as the negative electrode active material of the all-solid-state lithium ion secondary battery. For example, a lithium-aluminum alloy can be cited.

[0303] The negative electrode active material capable of forming an alloy with lithium has no particular limitation as long as it is a material commonly used as the negative electrode active material of the all-solid-state lithium ion secondary battery. As the above negative electrode active material, a negative electrode active material (alloy) containing silicon element or tin element and various metals such as Al and In can be cited. A negative electrode active material containing silicon element (active material containing silicon element) capable of achieving a higher battery capacity is preferred, and an active material containing silicon element with a silicon element content of 50 mol% or more of all constituent elements is more preferred.

[0304] Generally, a negative electrode containing these negative electrode active materials (e.g., a Si negative electrode containing an active material containing silicon element, a Sn negative electrode containing an active material containing tin element) can occlude more Li ions compared to a carbon negative electrode (graphite, acetylene black, etc.). That is, the occlusion amount of Li ions per unit mass increases. Therefore, the battery capacity can be increased. As a result, it has the advantage of being able to extend the battery driving time.

[0305] As the active material containing silicon element, for example, Si, SiO x (0 < x ≤ 1) and other silicon materials can be cited. In addition, silicon-containing alloys containing titanium, vanadium, chromium, manganese, nickel, copper, or lanthanum (e.g., LaSi2, VSi2, La-Si, Gd-Si, and Ni-Si) or organized active materials (e.g., LaSi2 / Si) can be cited. In addition, active materials containing silicon element and tin element such as SnSiO3 and SnSiS3 can be cited. In addition, regarding SiO x , it can be used as the negative electrode active material (semi-metal oxide) itself, and Si is generated through the operation of the all-solid-state lithium ion secondary battery. Therefore, it can be used as the negative electrode active material (its precursor material) capable of alloying with lithium.

[0306] As the negative electrode active material having tin element, for example, those containing Sn, SnO, SnO2, SnS, SnS2, and the above active materials containing silicon element and tin element can be cited.

[0307] From the viewpoint of battery capacity, the negative electrode active material is preferably a negative electrode active material that can alloy with lithium, more preferably the above-mentioned silicon material or an alloy containing silicon (alloy containing silicon element), and further preferably silicon (Si) or an alloy containing silicon.

[0308] As the negative electrode active material, titanium-niobium composite oxide is also preferably used. Titanium-niobium composite oxide has a high theoretical volume capacity density, and it can be expected to have a long life and can also be quickly charged. As titanium-niobium composite oxide, for example, TiNb2O7 ([TNO]) can be cited.

[0309] The shape of the negative electrode active material is not particularly limited, but preferably particulate. The volume average particle size of the negative electrode active material is not particularly limited, but preferably 0.1 to 60 μm, more preferably 0.5 to 20 μm, and further preferably 1.0 to 15 μm.

[0310] The volume average particle size is measured by the following procedure.

[0311] Use water (heptane in the case of unstable substances in water) to dilute the negative electrode active material in a 20 mL sample bottle to prepare a 1% dispersion. The diluted dispersion sample was irradiated with 1 kHz ultrasound for 10 minutes and then used in the test immediately. Using the dispersion sample and using a laser diffraction / scattering particle size distribution measuring device, 50 data readings were performed using a measuring quartz cell at a temperature of 25°C to obtain the volume average particle size. For other detailed conditions, refer to JIS Z 8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Make 5 samples for each level and use their average value.

[0312] The negative electrode active material may be used alone or in combination of two or more.

[0313] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is preferably 10 to 90 mass %, more preferably 20 to 85 mass %, further preferably 30 to 80 mass %, and particularly preferably 35 to 75 mass %.

[0314] The surface of the negative electrode active material may be coated with oxides such as other metal oxides or carbon-based materials, etc. These surface coating layers can function as interface resistance stabilizing layers.

[0315] As the surface coating agent, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si or Li can be cited. Specifically, titanate spinel, tantalum oxides, niobium oxides and lithium niobate compounds can be cited, for example, Li4Ti5O 12, Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3 and Li3AlF6. In addition, carbon-based materials such as C, SiC, and SiOC (carbon-doped silicon oxide) can also be used as surface coating materials.

[0316] Furthermore, the surface of the negative electrode active material may be surface-treated with sulfur or phosphorus.

[0317] Furthermore, the surface of the negative electrode active material may be subjected to a surface treatment using active light or active gas (for example, plasma) before or after the surface is coated.

[0318] Among these, TiNb2O7 (TNO), Li4Ti5O 12 (LTO) or Fe3O4 or these materials coated with an interface resistance stabilizing layer such as an oxide or carbon-based material.

[0319] (Negative electrode current collector layer)

[0320] The current collector layer constituting the negative electrode layer is an electron conductor and is usually in the form of a thin film sheet.

[0321] Examples of the constituent material of the negative electrode current collector layer include aluminum, aluminum alloys, copper, copper alloys, stainless steel, nickel, zinc, and titanium, and aluminum, aluminum alloys, and copper is preferred.

[0322] Examples of the negative electrode current collector layer include a negative electrode current collector layer having a coating layer (thin film) of carbon, nickel, zinc, titanium, aluminum, gold or silver on the surface of aluminum, copper, copper alloy or stainless steel.

[0323] The thickness of the negative electrode active material layer constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 5 to 500 μm, preferably 20 to 200 μm, and can also be, for example, 0.1 to 50 μm, and in this case, is preferably 1 to 20 μm.

[0324] The thickness of the negative electrode current collector layer constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 10 to 100 μm, preferably 10 to 50 μm, and can also be, for example, 0.01 to 20 μm, in which case, it is preferably 0.05 to 10 μm, and more preferably 0.1 to 5 μm.

[0325] (Current Collector Layer in Secondary Battery of the Present Invention)

[0326] In the secondary battery of the present invention, at least one of the positive electrode layer and the negative electrode layer includes a current collector layer, and at least one of the current collector layers is a layer having a metal that melts at 670° C. under normal pressure as a constituent material or a layer having the metal in a coating layer.

[0327] In the present invention or specification, "metal that melts at 670°C at normal pressure" means a metal that melts at 670°C under a pressure condition of 101.33 kPa, and means a metal having a melting point of 670°C or less at normal pressure.

[0328] Specifically, the “metal that melts at 670°C at normal pressure” includes Al (melting point at normal pressure is about 650-660°C) and Al alloy (melting point at normal pressure is about 480-650°C) recorded in the above-mentioned positive electrode collector layer, and Al (melting point at normal pressure is about 650-660°C) recorded in the above-mentioned negative electrode collector layer.

[0329] In addition, in all-solid-state lithium-ion secondary batteries using previous oxide-based solid electrolytes, although aluminum or aluminum alloys are sometimes cited as constituent materials of the collector layer or materials used in the coating, as mentioned above, since previous oxide-based solid electrolytes must be sintered at high temperatures, there is actually no all-solid-state lithium-ion secondary battery using previous oxide-based solid electrolytes that has a collector layer with aluminum or aluminum alloy as a constituent material or a collector layer with the metal in the coating.

[0330] The positive electrode layer and the negative electrode layer may contain components other than the solid electrolyte and the active material (other components) in their active material layers. For example, a conductive auxiliary agent may be contained.

[0331] As the conductive auxiliary agent, a substance generally known as a conductive auxiliary agent can be used. As the conductive auxiliary agent, for example, graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjen black and furnace black, amorphous carbon such as needle coke, fibrous carbon such as vapor-grown carbon fiber and carbon nanotubes, and carbonaceous materials such as graphene and fullerene can be cited as electron conductive materials. In addition, conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene and polyphenylene derivatives can be used.

[0332] In addition to the above-mentioned conductive additives, a common conductive additive containing no carbon atoms, such as metal powder or metal fiber, can be used.

[0333] A conductive aid is an aid that does not insert or release Li during battery charge and discharge and does not function as an active material. Therefore, among conductive aids, substances that function as active materials in the active material layer during battery charge and discharge are also classified as active materials rather than conductive aids. Whether or not a conductive aid functions as an active material during battery charge and discharge is not unique, but is determined by the combination with the active material.

[0334] The content of the conductive auxiliary agent in the positive electrode active material layer is not particularly limited, but is, for example, preferably 0 to 10% by mass, and more preferably 1 to 5% by mass.

[0335] The content of the conductive aid in the negative electrode active material layer is not particularly limited, but is, for example, preferably 0 to 10% by mass, and more preferably 1 to 5% by mass.

[0336] As other components, the above-mentioned binder and lithium salt can be mentioned.

[0337] <Manufacturing of all-solid-state lithium-ion secondary batteries>

[0338] The secondary battery of the present invention uses a solid electrolyte (I) at least in the solid electrolyte layer, and at least one of the positive electrode layer and the negative electrode layer includes a collector layer. As at least one of the collector layers, a layer having a specific metal as a constituent material or a layer having the metal in a coating layer is used. In addition, it can be manufactured with reference to the usual method for manufacturing a solid-state secondary battery. That is, the method for manufacturing a secondary battery of the present invention can include a step of obtaining a laminated body in which a positive electrode layer, a solid electrolyte layer and a negative electrode layer are sequentially arranged. Here, the amount of water in the solid electrolyte (I) used may or may not satisfy the amount specified in the present invention. In the method for manufacturing a solid-state secondary battery, regardless of the amount of water in the solid electrolyte (I) used, in order to set the amount of water of the solid electrolyte (I) contained in the structural layer such as the solid electrolyte layer to the amount specified in the present invention, in the manufacture of the secondary battery of the present invention, as needed, it is also possible to include a step of drying the formed solid electrolyte layer. The drying process of the structural layer such as the solid electrolyte layer can be carried out at any stage after the formation of the structural layer such as the solid electrolyte layer as long as the solid electrolyte (I) of the structural layer such as the solid electrolyte layer in the obtained secondary battery can be set to the amount of water specified in the present invention. In order to more reliably set the amount of water to the amount specified in the present invention, it is preferred to carry out the drying process at least in a state where the laminated body formed by sequentially configuring the positive electrode layer, the solid electrolyte layer and the negative electrode layer is configured in the battery cell. There is no particular limitation on the drying method, for example, a dryer can be used, or vacuum drying can be carried out, or freeze vacuum drying can be carried out, or heat treatment can be carried out, and the amount of water of the solid electrolyte (I) of the solid electrolyte layer can be reduced to within the range specified in the present invention.

[0339] The secondary battery of the present invention is preferably a secondary battery formed by sealing the laminated body formed by sequentially configuring the positive electrode layer, the solid electrolyte layer and the negative electrode layer. By sealing, it is possible to more reliably prevent moisture from mixing into the solid electrolyte layer after the above-mentioned drying process, thereby further improving the cycle characteristics. There is no particular limitation on the sealing method, as long as it can prevent or inhibit the mixing of moisture (atmosphere). For example, a method of sealing the laminated body by closing the cover of the shell (battery cell) storing the laminated body formed by sequentially configuring the positive electrode layer, the solid electrolyte layer and the negative electrode layer through a gasket such as an O-ring, etc. can be cited. In addition, the cell resistance can also be increased by heating the obtained laminated body (for example, at 80°C for 2 hours).

[0340] In one embodiment of the secondary battery manufacturing method of the present invention, at least one of the current collector layers included in at least one of the positive electrode layer and the negative electrode layer is a layer having a metal that melts at 670° C. at normal pressure as a constituent material or a layer having the metal in a coating layer.

[0341] As described above, at least the solid electrolyte layer of the secondary battery of the present invention is composed of the solid electrolyte (I), and no high-temperature sintering treatment is required, so as the constituent material of the collector layer or the metal contained in the coating, a metal that melts at 670° C. at normal pressure, which is difficult to use in conventional oxide-based solid electrolytes, can be used. The metal that melts at 670° C. at normal pressure is as described above.

[0342] Furthermore, in another embodiment of the manufacturing method of the secondary battery of the present invention, at least one of the collector layers included in at least one of the positive electrode layer and the negative electrode layer is a layer having Cu as a constituent material or a layer having Cu in a coating, and a stack of the positive electrode layer, the solid electrolyte layer and the negative electrode layer is manufactured in an atmosphere containing oxygen and at a temperature below 300°C.

[0343] As described above, at least the solid electrolyte layer of the secondary battery of the present invention is composed of a solid electrolyte (I), and no high-temperature sintering treatment is required, so even in an atmosphere containing oxygen, as the constituent material of the collector layer or the metal contained in the coating, Cu which is difficult to use in the conventional oxide-based solid electrolyte and will oxidize under high-temperature conditions containing oxygen can be used. As long as it is manufactured in an atmosphere containing oxygen and below 300°C, the oxidation of Cu can be suppressed by conditions such as heating time and heating temperature.

[0344] In general, the atmosphere containing oxygen includes air. The oxygen content is not particularly limited, but the upper limit can be 100 vol% or less, and the lower limit can be, for example, 1 vol% or more.

[0345] Manufacturing below 300°C means that the sintering process at high temperature required in the previous oxide-based solid electrolyte is essentially unnecessary. In the present invention, the secondary battery of the present invention can be manufactured by a manufacturing process below 300°C in an atmosphere containing oxygen, and can be manufactured in an atmosphere containing oxygen, preferably below 200°C, more preferably below 120°C, and further preferably below 100°C. Among them, it can be manufactured in an atmosphere containing oxygen, preferably below 80°C, more preferably at 60°C, further preferably at 40°C, and particularly preferably under non-heating conditions (for example, room temperature of 20 to 27°C).

[0346] Furthermore, there is no particular limitation on the method for forming a stacked body in which a positive electrode layer, a solid electrolyte layer, and a negative electrode layer are sequentially arranged.

[0347] As a method for manufacturing an all-solid-state secondary battery, for example, the following method can be cited: a positive electrode forming composition (positive electrode slurry) containing a positive electrode active material is applied to a metal foil as a positive electrode collector layer to form a positive electrode active material layer, then a solid electrolyte layer forming dispersion (solid electrolyte slurry) containing a solid electrolyte is applied to the positive electrode active material layer to form a solid electrolyte layer, and further, a negative electrode forming composition (negative electrode slurry) containing a negative electrode active material is applied to the solid electrolyte layer to form a negative electrode active material layer, and a negative electrode collector layer (metal foil) is overlapped on the negative electrode active material layer. The whole can be pressurized as needed to obtain a battery such as Figure 1 The all-solid-state lithium-ion secondary battery shown.

[0348] Furthermore, it is also possible to manufacture an all-solid-state lithium-ion secondary battery by reversing the method of forming each layer, forming a negative electrode active material layer, a solid electrolyte layer and a positive electrode active material layer on the negative electrode collector layer, and overlapping a positive electrode collector layer (metal foil) on the positive electrode active material layer, and pressurizing the entirety as needed.

[0349] As another method, the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer can be separately prepared, and they can be stacked in sequence between the positive electrode collector layer and the negative electrode collector layer as a positive electrode collector layer (metal foil), a positive electrode active material layer, a solid electrolyte layer, a negative electrode active material layer and a negative electrode collector layer (metal foil), and pressurized as needed to manufacture an all-solid-state lithium-ion secondary battery.

[0350] In this case, in the formation of each layer, supports such as nonwoven fabrics can be configured as required to make each layer a self-supporting film. In addition, usually, when stacking each layer and making a full solid-state lithium ion secondary battery, it is preferably used after removing the support in the self-supporting film.

[0351] In addition, as another method, it is also possible to use a powder constituting a positive electrode active material layer (hereinafter referred to as a powder of a positive electrode composite material), a powder constituting a solid electrolyte layer (hereinafter referred to as a powder of a solid electrolyte), and a powder constituting a negative electrode active material layer (hereinafter referred to as a powder of a negative electrode composite material), and pressurize the powders constituting each layer separately to make them into a specified shape, thereby forming particles of each layer, and by overlapping and pressurizing the collector layers of the positive electrode or the negative electrode, an all-solid-state lithium-ion secondary battery is manufactured.

[0352] For example, by filling a solid electrolyte powder into a predetermined mold and performing pressure molding to form solid electrolyte particles, filling a negative electrode composite material powder onto one surface of the obtained solid electrolyte particles and performing pressure molding to form negative electrode composite material particles, and filling a positive electrode composite material powder onto the other surface of the obtained solid electrolyte particles and performing pressure molding to form positive electrode composite material particles, thereby obtaining a pressed powder molded body in which the positive electrode composite material particles, solid electrolyte particles, and negative electrode composite material particles are sequentially stacked. Next, the negative electrode current collector layer (metal foil) can be overlapped in such a manner that the negative electrode composite material particles of the obtained pressed powder molded body are on the lower side, and the positive electrode current collector layer (metal foil) is overlapped on the upper side of the positive electrode composite material particles, and the whole is pressurized to obtain a pressed powder molded body as shown in FIG. Figure 1 The all-solid-state lithium-ion secondary battery shown.

[0353] The method for preparing the solid electrolyte powder is not particularly limited, and for example, the powder can be prepared by freeze-vacuum drying a solid electrolyte layer-forming dispersion liquid (solid electrolyte slurry) containing a solid electrolyte.

[0354] The method for preparing the powder of the negative electrode composite material is not particularly limited, and it can be prepared, for example, by mixing previously prepared solid electrolyte powder and components for forming a negative electrode active material layer including a negative electrode active material.

[0355] The method for preparing the powder of the positive electrode composite material is not particularly limited, and it can be prepared, for example, by mixing previously prepared solid electrolyte powder and components for forming a positive electrode active material layer including a positive electrode active material.

[0356] The pressurizing conditions for preparing the negative electrode composite material particles, the solid electrolyte particles, and the positive electrode composite material particles are not particularly limited. For example, the particles can be prepared by applying a pressure of 50 to 300 MPa for about 10 seconds.

[0357] Furthermore, the pressure bonding between the negative electrode composite material particles and the negative electrode current collector layer and the pressure bonding between the positive electrode composite material particles and the positive electrode current collector layer can also be performed by applying a pressure of about 60 MPa.

[0358] The order of forming the particles of each layer is not particularly limited. For example, the particles of the negative electrode composite material, the particles of the solid electrolyte, and the particles of the positive electrode composite material may be formed in this order.

[0359] As another method, particles of the negative electrode composite material, particles of the solid electrolyte, and particles of the positive electrode composite material can be separately prepared, and the obtained particles can be stacked and pressurized in a manner such that the stacked particles are sandwiched between the collector layers of the positive and negative electrodes, thereby manufacturing an all-solid-state lithium-ion secondary battery.

[0360] Furthermore, regarding the manufacturing method of a small stacked battery formed by stacking a plurality of positive electrode layers, solid electrolyte layers, and negative electrode layers in a manner of configuring a solid electrolyte layer between adjacent positive electrode layers and negative electrode layers, for example, it can be manufactured with reference to the stacking method described in paragraphs

[0033] to

[0046] of Japanese Patent Publication No. 2016-001602. In addition, regarding the manufacturing method of each layer of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer, it can be manufactured according to the manufacturing method of the present invention described above.

[0361] In addition, the manufacturing method of the secondary battery of the present invention is not limited to the manufacturing method described above as long as the secondary battery specified in the present invention can be obtained.

[0362] In the manufacture of the secondary battery of the present invention, even if a sulfide-based solid electrolyte is not used as the solid electrolyte, the formation of a layer that suppresses the interface resistance between solid particles or between layers can be achieved through the action of the above-mentioned oxide-based solid electrolyte (I) that can easily undergo plastic deformation under pressure.

[0363] The solid electrolyte (I) itself is soft and plastically deformable, and acts like a binder to help improve the adhesion between solid particles and between layers. Therefore, it is possible to form layers without using a binder such as an organic polymer.

[0364] The secondary battery of the present invention is preferably initialized after manufacture or before use. The initialization method is not particularly limited, and can be performed by, for example, performing initial charge and discharge under increased pressure and then releasing the pressure until the pressure condition is within the range when the secondary battery is used.

[0365] <Applications of all-solid-state lithium-ion secondary batteries>

[0366] The secondary battery of the present invention can be applied to various purposes. The application mode is not particularly limited. For example, when it is carried on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone handset, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a video movie, a liquid crystal television, a handheld cleaner, a portable CD player, a mini disc player, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio and a backup power supply can be cited. As other consumer products, automobiles, electric vehicles, motors, lighting equipment, toys, game consoles, load regulators, clocks, flashlights, cameras and medical equipment (pacemakers, hearing aids and shoulder massagers, etc.) can be cited. In addition, it can be used for various military purposes and space purposes. And, it can also be combined with solar cells.

[0367] Example

[0368] The present invention will be further described in detail with reference to the examples, but the interpretation of the present invention is not limited thereto. In the present invention, room temperature refers to 27° C. Furthermore, the manufacture of the solid electrolyte or the manufacture of the secondary battery described below is performed in an atmosphere in which moisture and oxygen exist in the atmosphere.

[0369] [Reference Example 1: Production based on the above steps 0, 1A to 3A]

[0370] Using a ball mill (manufactured by Fritsch Japan Co., Ltd., planetary ball mill P-7), powdered Li2B4O7 crystals (LBO powder) (manufactured by RARE METALLIC Co., Ltd.) were ball-milled under the following conditions: pot: yttria-stabilized zirconia (YSZ) (45 mL), grinding balls: YSZ (average particle size: 5 mm, number: 50), rotation speed: 370 rpm (revolutions per minute), LBO powder amount: 1 g, atmosphere: air, ball mill processing time: 100 hours, thereby obtaining a micronized lithium-containing oxide (hereinafter also referred to as "micronized lithium-containing oxide").

[0371] 0.05 g of LiFSI (chemical formula: Li(FSO2)2N) was added as a lithium salt to 1 g of the obtained lithium oxide-containing fine material (5% by mass relative to the lithium oxide-containing fine material), and ball milling was performed for 100 hours. The obtained powder was added to water so that the powder concentration became 42% by mass, and ultrasonic dispersion was performed for 30 minutes. Then, the obtained dispersion was transferred to a glass petri dish and dried at 120°C for 2 hours in the atmosphere to obtain a thin film of a solid electrolyte. Then, the obtained film was peeled off to obtain a powdery solid electrolyte (I)-1.

[0372] <Production and evaluation of solid electrolyte molded body>

[0373] The powdered solid electrolyte (I)-1 obtained above was pressed at 27°C (room temperature) at an effective pressure of 220 MPa to obtain a solid electrolyte molded body (compressed powder body 1). The shape of the compressed powder body 1 was a cylindrical shape with a diameter of 10 mm and a thickness of 1 mm. The ionic conductivity of the compressed powder body 1 was measured and the ionic conductivity of the compressed powder body 1 was 1.5×10 -4 S / cm, and 4.0×10 at 60°C -4 S / cm.

[0374] The ionic conductivity of the above-mentioned solid electrolyte (I)-1 was calculated by the following method: electrodes consisting of two In foils were arranged in a manner of clamping the powder compact 1, and the AC impedance between the two In electrodes was measured in the measurement frequency range of 1 Hz to 1 MHz at a measurement temperature of 27°C or 60°C and an applied voltage of 50 mV, and the arc diameter of the obtained Cole-Cole diagram (Nyquist diagram) was analyzed.

[0375] As described above, using CuKα rays, X-ray diffraction measurement of solid electrolyte (I)-1 was performed. The measurement conditions were set to 0.01° / step and 3° / minute. The results showed that the above-mentioned X-ray diffraction characteristics were satisfied, which showed that solid electrolyte (I)-1 was in an amorphous state.

[0376] The solid electrolyte (I)-1 obtained in the above was used and the solid electrolyte (I)-1 was measured by SPring-8L04B2 (accelerating voltage: 61.4 keV, wavelength: ) Total X-ray scattering measurements were performed. The samples were sealed in a 2 mm φ or 1 mm φ Kapton capillary and the experiment was performed. As described above, the obtained data were Fourier transformed to obtain the reduced two-body distribution function.

[0377] As a result of the analysis, it was confirmed that in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement, when r is In the range of , the peak G(r) shows more than 1.0, and the peak is located at The first peak and the peak G(r) show more than 1.0, and the peak is located at The second peak of

[0378] On the other hand, in solid electrolyte (I)-1, the peaks attributed to the BO distance and BB distance observed in ordinary lithium tetraborate crystals are maintained. Ordinary lithium tetraborate crystals have a structure (diborate structure) in which BO4 tetrahedrons and BO3 triangles exist in a 1:1 ratio, and it is inferred that in solid electrolyte (I)-1, its structure is maintained.

[0379] Solid electrolyte (I)-1 was prepared at 120 °C. 7 The full width at half maximum (FWHM 2) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained by Li-NMR measurement is relative to the solid electrolyte (I)-1 obtained above at 20°C. 7 The ratio of the full width at half maximum (FWHM 1) of the peak whose chemical shift appeared in the range of -100 to +100 ppm in the spectrum obtained in Li-NMR measurement {(FWHM 2 / FWHM 1)×100} was 33%.

[0380] And, solid state at 20°C 7 When the waveform of the first peak appearing in the range of -100 to +100 ppm in the spectrum obtained during Li-NMR measurement is separated, a second peak having a chemical shift in the range of -3 to +3 ppm and a half-maximum width of less than 5 ppm is obtained, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 4%.

[0381] The solid electrolyte (I)-1 obtained in the above-mentioned manner was used and infrared absorption spectrum was measured under the above-mentioned conditions. In the infrared absorption spectrum obtained, the -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The ratio of the maximum absorption intensity in the wavenumber region is 0.72.

[0382] In the Raman spectrum of the solid electrolyte (I)-1 obtained above, the -1 The coefficient of determination obtained by least squares linear regression analysis in the wavenumber region is 0.9974.

[0383] As described above, the mass reduction rate when the solid electrolyte (I)-1 was heated from 25°C to 800°C was 29.8%.

[0384] Regarding the analysis of each element in the obtained solid electrolyte (I)-1, lithium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC), and regarding N, the analysis mass of sulfur was estimated in consideration of each atomic weight in the Li salt, and regarding O, the analysis mass of the elements other than O was added and calculated as a difference from the total amount of powder. The results are shown in the following table.

[0385] [Reference Example 2: Production based on the above steps 1B to 3B and method 2]

[0386] 1 g of the lithium oxide-containing fine substance used in Reference Example 1 was added to water so that the concentration of the fine substance became 42 mass %, and ultrasonic dispersion was performed for 30 minutes. 0.05 g of LiFSI (chemical formula: Li(FSO2)2N) was added to the obtained dispersion as a lithium salt (5 mass % relative to the lithium oxide-containing fine substance), and ultrasonic dispersion was performed for 30 minutes.

[0387] The obtained dispersion was transferred to a glass petri dish and dried at 120° C. for 2 hours in the atmosphere to obtain a thin film of a solid electrolyte. Next, the obtained thin film was peeled off to obtain a powdered solid electrolyte (I)-2. Regarding the solid electrolyte (I)-2, various evaluations were performed in the same manner as in Reference Example 1 in the atmosphere. The results are summarized in the following table.

[0388] [Reference Example 3: Production based on the above steps 1B to 3B and method 3]

[0389] Using a ball mill (manufactured by Fritsch Japan Co., Ltd., planetary ball mill P-7), powdered Li2B4O7 (LBO powder) (manufactured by RARE METALLIC Co., Ltd.) was ball milled under the conditions of pot: YSZ (45 ml), grinding balls: YSZ (average particle size: 5 mm, weight: 70 g), rotation speed: 530 rpm (revolutions per minute), LBO powder amount: 4.2 g, atmosphere: air, and ball mill processing time: 100 hours to obtain a fine substance containing lithium oxide.

[0390] The obtained lithium oxide-containing fine substance was added to water so that the concentration of the fine substance became 42 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a dispersion liquid 1.

[0391] Next, 3.25 g of LiFSI (chemical formula: Li(FSO 2 ) 2 N) as a lithium salt was added to water so as to have a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 2 .

[0392] The obtained dispersion 1 and solution 2 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-3. The obtained powder was allowed to stand for a certain period of time in the atmosphere, and various evaluations were performed in the same manner as in Reference Example 1 using the solid electrolyte (I)-3 in the atmosphere. The results are summarized in the following table.

[0393] [Reference Example 4: Production based on the above steps 1B to 3B and method 3]

[0394] In the same manner as in the preparation of Dispersion Liquid 1 in Reference Example 3, Dispersion Liquid 3 was obtained.

[0395] Next, 2.32 g of LiFSI (chemical formula: Li(FSO 2 ) 2N) as a lithium salt was added to water at a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 4 .

[0396] The obtained dispersion 3 and solution 4 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-4. The obtained powder was allowed to stand for a certain period of time under the atmosphere, and various evaluations were performed under the atmosphere using the solid electrolyte (I)-4 in the same manner as in Reference Example 1. The results are summarized in the following table.

[0397] [Reference Example 5: Production based on the above steps 1B to 3B and method 3]

[0398] In the same manner as in the preparation of Dispersion Liquid 1 in Reference Example 3, Dispersion Liquid 5 was obtained.

[0399] Next, 4.65 g of LiFSI (chemical formula: Li(FSO 2 ) 2 N) as a lithium salt was added to water at a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 6 .

[0400] The obtained dispersion 5 and solution 6 were mixed and stirred for 60 minutes using a magnetic stirrer. Next, the obtained dispersion was vacuum dried at 40° C. and 10 Pa for 15 hours to obtain a powdered solid electrolyte (I)-5. The obtained powdered solid electrolyte (I)-5 was immediately used to perform various evaluations in the same manner as in Reference Example 1 under the atmosphere. The results are summarized in the following table.

[0401] [Reference Example 6: Production based on the above steps 1B to 3B and method 3]

[0402] In the same manner as in the preparation of Dispersion Liquid 1 in Reference Example 3, Dispersion Liquid 7 was obtained.

[0403] Next, 7.13 g of LiTFSI (chemical formula: Li(F3CSO2)2N) as a lithium salt was added to water at a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 8.

[0404] The obtained dispersion 7 and solution 8 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-6. The obtained powder was allowed to stand for a certain period of time under the atmosphere, and various evaluations were performed under the atmosphere using the solid electrolyte (I)-6 in the same manner as in Reference Example 1. The results are summarized in the following table.

[0405] In Reference Example 6, the carbon content shown in Table 1 below was estimated from the analyzed mass of sulfur in consideration of the atomic weights of the lithium salt.

[0406] [Comparative Reference Example 1]

[0407] The elemental analysis of the LBO powder (Li2B4O7 crystals in powder form without ball milling) used in Reference Example 1 showed that the composition of the LBO powder obtained was Li 1.96 B 4.00 O 6.80 The LBO powder was compacted at 27° C. (room temperature) at an effective pressure of 220 MPa to obtain a comparative reference powder compact C1. The ion conductivity of the obtained powder compact C1 could not be detected.

[0408] Furthermore, in the same manner as in Reference Example 1, total X-ray scattering measurement was performed using LBO powder to obtain the reduced two-body distribution function G(r). Fig.10 In FIG. 1 , the reduced two-body distribution function G(r) obtained from total X-ray scattering measurements is shown.

[0409] The analysis results show that in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of LBO powder, there is a peak located at The first peak (corresponding to the vicinity of BO) and the peak are located at The second peak of the BB (corresponding to the BB), the peak G (r) of the first peak and the second peak are both above 1.0 (reference Fig.10 ). In addition, there is a peak located at and The absolute value of the peak G(r) of each peak obviously exceeds 1.0 (ref. Fig.10 ).

[0410] Using CuKα rays, X-ray diffraction measurement was performed on the LBO powder of Comparative Reference Example 1. The measurement conditions were 0.01° / step and 3° / minute.

[0411] exist Fig.11 , the X-ray diffraction pattern of the LBO powder of Comparative Reference Example 1 is shown. Fig.11 As shown, in the LBO powder used in comparative reference example 1, multiple small peaks of width were observed. More specifically, the strongest peak corresponding to the (1,1,2) plane was observed at a position with a 2θ value of 21.78°. As other major diffraction peaks, a peak corresponding to the (2,0,2) plane was shown at a position of 25.54°, a peak corresponding to the (2,1,3) plane was shown at a position of 33.58°, and a peak corresponding to the (3,1,2) plane was shown at a position of 34.62°, and the intensities of these three peaks were roughly the same. These peaks originate from the crystal components.

[0412] [Comparative Reference Example 2]

[0413] The result of elemental analysis of the fine material containing lithium oxide prepared in Reference Example 1 (the material obtained by ball milling powdered Li2B4O7 crystals) showed that the composition of the fine material containing lithium oxide was Li 1.94 B 4.00 O 6.80 .

[0414] Next, the lithium oxide-containing fine material was pressed at 27°C (room temperature) at an effective pressure of 220 MPa to obtain a powder compact (powder compact R1) for comparative reference. The ion conductivity of the obtained powder compact R1 at 27°C was 7.5×10 -9 S / cm, and 7.5×10 at 60°C -8 S / cm.

[0415] In the following table, as described above, in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement, there is a peak located at r The first peak and the peak top in the range of r are If the peak G(r) of the first peak and the peak G(r) of the second peak show a value greater than 1.0, the "Short-range G(r)" column is set to "A", and all other cases are set to "B".

[0416] In Reference Examples 1 to 5 and Reference Examples 9 to 13 shown in the following table, the value of the peak top G(r) of the first peak was 1.2 or more.

[0417] Furthermore, in the above-mentioned reduced two-body distribution function G(r), when r is greater than and When the absolute value of G(r) in the following range is less than 1.0, the "Long-range G(r)" column in the following table is set to "A", and when the absolute value of G(r) does not satisfy less than 1.0, it is set to "B".

[0418] In addition, the result of the X-ray diffraction measurement using the above-mentioned CuKα ray is set as "A" when the above-mentioned X-ray diffraction characteristics are satisfied, and "B" when the above-mentioned X-ray diffraction characteristics are not satisfied. In addition, in Reference Examples 1 to 6 shown in the following table and Reference Examples 7 to 13 described later, in the X-ray diffraction spectrum, the first peak, the second peak, the third peak, and the fourth peak are not present, or the intensity ratio of at least one of the first peak, the second peak, the third peak, and the fourth peak is 2.0 or less.

[0419] In the following table, in the "Elemental Analysis" column, the molar content of each element is shown as a relative value with the B content being "4.00" for the composition of the solid electrolyte (I) obtained in each reference example and the lithium-containing oxide in each comparative reference example.

[0420] In the following table, blank means that the corresponding element is not contained.

[0421] In the following table, "half width ratio (%)", "coefficient of determination" and "mass reduction rate (%)" are the same as those described in the above description of Reference Example 1.

[0422] In the following table, the “area intensity ratio” is the ratio of the above solid state 7 In the Li-NMR measurement, the ratio of the area intensity of the second peak to the area intensity of the first peak was measured, and the evaluation results were described based on the following criteria.

[0423] <Standards for the ratio of area strength>

[0424] A: When the area strength ratio is 15% or more

[0425] B: When the ratio of area strength is 0.5% or more and less than 15%

[0426] C: When the ratio of area intensity is less than 0.5%

[0427] In the following table, the "Maximum Absorption Intensity Ratio" column indicates whether the above infrared absorption spectrum characteristics are met. -1 The maximum absorption intensity in the wave number region of 800 to 1600 cm -1 When the maximum absorption intensity in the wave number region is greater than 0.20, it is represented as "A", and when it is less than 0.20, it is represented as "B".

[0428] In the following table, "-" means that the measured value is not shown.

[0429] [Table 1]

[0430]

[0431] [Table 2]

[0432]

[0433] As shown in the above table, it can be seen that the solid electrolytes (I)-1, (I)-2, (I)-3, (I)-4, (I)-5 and (I)-6 of Reference Examples 1 to 6 have the desired characteristics or physical properties and excellent ion conductivity. In addition, according to the results of elemental analysis, it is confirmed that the content of Li in the solid electrolyte is higher in Reference Examples 3 to 6. In Reference Examples 3 to 6, an aqueous dispersion containing a lithium oxide treated by mechanical grinding and an aqueous solution containing a lithium salt (method 3 in the above-mentioned step 2B) are mixed, and more lithium salts can be mixed. As a result, it is speculated that the amount of Li entering the solid electrolyte has increased. In addition, it can be seen that in Reference Examples 3, 4 and 5 using LiFSI as a lithium salt, the ion conductivity is further improved. It is speculated that this is because the increased Li contains Li with high mobility.

[0434] <Effect of water in solid electrolyte>

[0435] The solid electrolyte (I)-3 powder compact (granules) (10 mmφ, 0.9 mmt (thickness)) obtained in Reference Example 3 was vacuum dried at 27°C under a constraint of 60 MPa, and the pressure change and ion conductivity relative to the vacuum drying time were investigated. In addition, the method for preparing the powder compact and the evaluation of ion conductivity were the same as described above, except that the In electrode was changed to a Ti electrode. The results are shown in Table 3.

[0436] [Table 3]

[0437]

[0438] The solid electrolyte (I)-3 of Reference Example 3 has a wavelength of 3000-3500 cm in the infrared absorption spectrum. -1 In the wave number region of , a strong absorption intensity originating from the OH stretching peak was observed, so it is believed that a large amount of OH groups or water exists. In addition, regarding water, it is inferred that there are free water and bound water. In the above, the particles were first dried under conditions that are believed to volatilize from free water by vacuum drying, and then the particles were dried under strict drying conditions, so that the ion conductivity at each stage was evaluated.

[0439] As shown in the above table, the drying time was 5 minutes and the pressure was 200 Pa. It is considered that the free water was in a state of evaporation, but the ion conductivity showed 3.8×10 -3 S / cm, and the ionic conductivity showed 5.7×10 -4 S / cm. This result indicates that bound water in addition to free water exists and this contributes to ion conductivity.

[0440] [Reference Example 7: Production based on the above steps 1B to 3B and method 3]

[0441] In the same manner as in the preparation of the dispersion 1 in the above-mentioned Reference Example 3, a dispersion 9 having a concentration of 42% by mass of fine substances containing lithium oxide was obtained.

[0442] Next, 7.12 g of LiTFSI (chemical formula: Li(F 3 CSO 2 ) 2 N) as a lithium salt was added to water so as to have a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 10 .

[0443] The obtained dispersion 9 and solution 10 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-7. The obtained powder was allowed to stand for a certain period of time under the atmosphere, and various evaluations were performed under the atmosphere using the solid electrolyte (I)-7 in the same manner as in Reference Example 1. The results are summarized in the following table.

[0444] [Reference Example 8]

[0445] Solid electrolyte (I)-8 was obtained in the same manner as Reference Example 7 except that the contents of water and LiTFSI in the obtained solid electrolyte (I) were changed to the amounts described in the following table, and various evaluations were performed under air in the same manner as Reference Example 1. The results are summarized in the following table.

[0446] [Reference Examples 9 to 13]

[0447] Except that LiTFSI was changed to LiFSI and the contents of water and LiFSI in the obtained solid electrolyte (I) were changed to the amounts described in the following table, solid electrolytes (I)-9 to (I)-13 were obtained in the same manner as in Reference Example 7, and various evaluations were performed in the same manner as in Reference Example 1 under the atmosphere. The results are summarized in the following table. However, in Reference Example 13, the powder obtained by vacuum drying was immediately used and the evaluation was performed in the atmosphere.

[0448] In the following table, the columns "fine matter containing lithium oxide", "lithium salt" and "water" indicate relative molar ratios. For example, in Reference Example 7, the molar ratio of lithium salt to fine matter containing lithium oxide is 1, and the molar ratio of water to fine matter containing lithium oxide is 11. The above molar ratios were calculated by the following method.

[0449] Regarding the analysis of each element, lithium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC). Regarding N, it was estimated based on the analytical mass of sulfur in consideration of each atomic weight in the Li salt, and regarding O, the analytical masses of elements other than O were added and calculated as a difference from the total amount of the solid electrolyte. In addition, in Reference Examples 7 and 8, regarding the carbon content, it was estimated based on the analytical mass of sulfur in consideration of each atomic weight in the lithium salt. The molar ratio of the fine matter containing lithium oxide in the solid electrolyte to the lithium salt was calculated based on the molar ratio of the element (e.g., B) present only in the fine matter containing lithium oxide to the element present only in the lithium salt. In addition, the molar ratio of the fine matter containing lithium oxide to water was calculated by subtracting the molar ratio of O contained in the fine matter containing lithium oxide and the lithium salt from the molar ratio of O in the solid electrolyte, and the molar amount of O derived from water was calculated using the obtained molar amount of O derived from water and the molar amount of the fine matter containing lithium oxide.

[0450] [Table 4]

[0451] Fine matter containing lithium oxide Lithium salts water Comparative Reference Example 2 1 0 0 Reference Example 7 1 1 11 Reference Example 8 1 1.2 11 Reference Example 9 1 0.01 4 Reference Example 10 1 0.03 4 Reference Example 11 1 0.5 11 Reference Example 12 1 0.7 11 Reference Example 13 1 1.0 6

[0452] Then, the content (mass %) of each component in the solid electrolyte (I) was calculated based on the molar amount and molecular weight described in Table 4. The results are shown in Table A below.

[0453] [Table A]

[0454] Fine matter containing lithium oxide Lithium salts water Comparative Reference Example 2 100 0 0 Reference Example 7 26 44 30 Reference Example 8 24 48 28 Reference Example 9 70 1 29 Reference Example 10 69 2 29 Reference Example 11 37 20 43 Reference Example 12 34 26 40 Reference Example 13 36 40 24

[0455] [Table 5]

[0456]

[0457] As shown in the above table, the solid electrolyte of each reference example satisfies the composition specified in claim 1 of the present application, has desired characteristics or properties, and exhibits excellent ion conductivity.

[0458] [Manufacturing Example 1] Manufacture of Coated Secondary Battery

[0459] <Preparation of fine material containing lithium oxide>

[0460] 45 g of powdered Li2B4O7 crystals (LBO powder) (manufactured by RARE METALLIC Co., Ltd.), 770 g of zirconium oxide beads and 3 mL of water were placed in a 500 mL zirconium oxide jar and sealed with a ring made of Teflon (registered trademark) and a lid made of zirconium oxide. The LBO powder was milled at 300 rpm (revolutions per minute) for 45 hours using a star ball mill (P-7, manufactured by Fritsch Japan Co., Ltd.) to obtain a fine substance containing lithium oxide.

[0461] <Preparation of solid electrolyte slurry: Preparation of solid electrolyte (I) by the above steps 1B to 3B and method 1>

[0462] 10 g of the lithium oxide-containing fine material, 15 g of water, and 11 g of LiFSI were mixed in a beaker and subjected to ultrasonic treatment for 30 minutes using an ultrasonic cleaner to obtain a dispersion liquid. The dispersion liquid was further stirred for 30 minutes using a magnetic stirrer to obtain a solid electrolyte slurry 1.

[0463] The solid electrolyte slurry 1 was vacuum dried at 40°C and 20Pa for 15 hours to obtain a powder. The obtained powder was stored in a dryer (humidity 5%) for several days and then analyzed in the atmosphere. As a result, it was confirmed that it had the above-mentioned X-ray diffraction characteristics and was in an amorphous state. In addition, the ion conductivity was measured by the above method and the result was 4.5×10 -3 S / cm. The molar ratio of the content of LiFSI to the content of the lithium-containing oxide is 1, and the molar ratio of the content of water to the content of the lithium-containing oxide is 9. The element composition is Li=3, B=4, O=20, F=2, S=2, and N=1.

[0464] <Preparation of positive electrode slurry>

[0465] 5.0 g of positive electrode active material LiCoO2 (volume average particle size 12 μm) and 4.8 g of a 6 mass % aqueous dispersion of carbon nanotubes (CNT) (manufactured by KJ Specialty Paper Co., LTD.) as a conductive aid were added to 5.2 g of the above-mentioned solid electrolyte slurry 1, and stirred with a magnetic stirrer for 30 minutes to obtain positive electrode slurry 1.

[0466] <Preparation of negative electrode slurry>

[0467] 5.0 g of negative electrode active material TiNb2O7 (volume average particle size 10 μm) and 9.8 g of a 6 mass % aqueous dispersion of CNT (manufactured by KJ Specialty Paper Co., LTD.) as a conductive aid were added to 7.6 g of the above-mentioned solid electrolyte slurry 1, and stirred with a magnetic stirrer for 30 minutes to obtain negative electrode slurry 1.

[0468] <Preparation of positive electrode stack [solid electrolyte layer / positive electrode active material layer / Al current collector layer]>

[0469] Using a desktop coater, the above-mentioned positive electrode slurry 1 is coated on an A4-sized Al foil with a thickness of 50 μm at a coating gap of 100 μm and a coating speed of 30 mm / s. After standing at room temperature for 1 hour, the above-mentioned solid electrolyte slurry 1 is multi-layered and coated on the positive electrode slurry coating film using a desktop coater with a coating gap of 200 μm and a coating speed of 90 mm / s. The multi-layer coating film is kept in a dryer with a relative humidity of less than 5% for 12 hours for drying, and punched into a diameter of 10 mm with a manual puncher, thereby obtaining a positive electrode side laminate (solid electrolyte layer / positive electrode active material layer / Al collector layer). In addition, the thickness of the solid electrolyte layer is about 60 μm.

[0470] <Preparation of negative electrode stack [solid electrolyte layer / negative electrode active material layer / Al current collector layer]>

[0471] Using a desktop coater, the above-mentioned negative electrode slurry 1 is coated on an A4-sized Al foil with a thickness of 50 μm at a coating gap of 200 μm and a coating speed of 30 mm / s. After standing at room temperature for 1 hour, the above-mentioned solid electrolyte slurry 1 is multi-layered and coated on the negative electrode slurry coating film using a desktop coater with a coating gap of 300 μm and a coating speed of 90 mm / s. The multi-layer coating film is kept in a dryer with a relative humidity of less than 5% for 12 hours for drying, and punched into a diameter of 10 mm with a manual puncher to obtain a negative electrode side laminate (solid electrolyte layer / negative electrode active material layer / Al collector layer). In addition, the thickness of the solid electrolyte layer is about 60 μm.

[0472] <Manufacturing of coating type secondary battery>

[0473] The negative electrode side stack obtained above was placed on a 10 mm diameter SUS table of an all-solid-state battery evaluation cell (product name: KP-SolidCell) manufactured by Hohsen Corp. with the solid electrolyte layer side facing upward, and the positive electrode side stack obtained above was placed on top of it with the solid electrolyte layer side facing downward.

[0474] Next, a tube made of Teflon (registered trademark) with an inner diameter of 10.2 mm (hereinafter referred to as the Teflon tube) is inserted from the upper side (positive electrode side stack side) of the battery cell A formed by stacking the positive electrode side stack / negative electrode side stack in sequence, and a 10 mm diameter, 2 mm thick polished Ti plate is inserted into the hole in the upper part of the Teflon tube and placed on the positive electrode stack. In addition, a Ti rod with a diameter of 10 mm and a height of 2 cm is inserted and placed on the Ti plate.

[0475] Next, the upper shell of KP-SolidCell was inserted and sealed with double O-rings, four-point bolts and butterfly nuts. The restraint pressure applying mechanism laid on the upper part of KP-SolidCell restrained the battery cell A from top and bottom with a torque of 5Nm (equivalent to 30MPa).

[0476] Next, the KP-SolidCell was temporarily opened and the battery cell A was taken out. After wiping off the excess liquid components that had seeped out due to the application of the restraining pressure, the battery cell A was again placed in the KP-SolidCell in the same manner as above, and the restraining pressure was applied with a torque of 5 Nm (equivalent to 30 MPa).

[0477] Then, with the upper cover open, freeze vacuum drying was performed for 2 hours to fully remove the moisture inside the battery cell A. After taking out the KP-SolidCell from the vacuum dryer, the upper cover was closed and sealed with a double O-ring. The coated secondary battery A was prepared by leaving it at room temperature for 40 hours.

[0478] In the preparation of the above-mentioned coated secondary battery A, a 50μm thick A4-sized Ti foil was used instead of a 50μm thick A4-sized Al foil as the collector layer in the positive electrode, and a 50μm thick A4-sized Cu foil was used instead of a 50μm thick A4-sized Al foil as the collector layer in the negative electrode. Except for this, a coated secondary battery B was prepared in the same manner as the above-mentioned coated secondary battery A.

[0479] In the coating type secondary batteries A and B, the thickness of the positive electrode active material layer was 80 μm, the thickness of the solid electrolyte layer was 120 μm, and the thickness of the negative electrode active material layer was 100 μm.

[0480] [Manufacturing Example 2] Manufacture of a compressed powder type secondary battery

[0481] <Preparation of solid electrolyte powder 1: Preparation of solid electrolyte (I) by the above steps 1B to 3B and method 1>

[0482] 10 g of the lithium oxide-containing fine material prepared in the above-mentioned manufacturing example 1, 15 g of water and 11 g of LiFSI were mixed in a beaker, and ultrasonic treatment (dispersion) was performed using an ultrasonic cleaner for 30 minutes, and then further stirred and dispersed for 30 minutes using a magnetic stirrer to obtain a solid electrolyte slurry. The obtained slurry was freeze-vacuum dried at 40° C. and 10 Pa for 12 hours to obtain a solid electrolyte powder 1.

[0483] <Preparation of positive electrode composite material powder 1>

[0484] 100 mg of the above-mentioned solid electrolyte powder 1, 150 mg of positive electrode active material LiCoO 2 (volume average particle size 12 μm), and 3 mg of conductive auxiliary agent carbon black (manufactured by Denka Company Limited.) were mixed in a mortar to obtain positive electrode composite material powder 1.

[0485] <Preparation of negative electrode composite material powder 1>

[0486] 60 mg of the above solid electrolyte powder 1, 120 mg of negative electrode active material cLTO (LTO with a carbon coating layer, volume average particle size of 10 μm), and 3 mg of conductive aid carbon black (manufactured by Denka Company Limited.) were mixed in a mortar to obtain negative electrode composite material powder 1.

[0487] <Manufacturing of powder compact>

[0488] A 10 mm diameter SUS punch (short ruler) was inserted into the hole at the bottom of a SUS tube (10 mm inner diameter) for powder compacting, and the above-mentioned solid electrolyte powder 1 was placed in the hole at the top of the SUS tube and made uniform. A SUS punch (long) was inserted from the top hole and pressurized at 50 MPa for 10 seconds using a hydraulic press, and then the pressure was released and the SUS punch (long strip) was pulled out of the SUS tube.

[0489] Next, the negative electrode composite material powder 1 was put into the hole at the top of the SUS tube and evenly spread on the pressed powder layer of the solid electrolyte powder 1. The SUS punch (long) was inserted from the hole at the top and pressurized at 50 MPa for 10 seconds using a hydraulic press. After releasing the pressure, the state of SUS punch (long) / SUS tube / SUS punch (short) was turned upside down from the top to the bottom, so that the SUS punch (short) was on the top, and then the SUS punch (short) was pulled out from the SUS tube.

[0490] The positive electrode composite material powder 1 was put into the hole at the top of the SUS tube and evenly spread on the compressed powder layer of the solid electrolyte powder 1. A SUS punch (short ruler) was inserted from the hole at the top and a hydraulic press was used to pressurize at 200 MPa for 10 seconds, then the pressure was released, and a pressed powder molded body formed by stacking the compressed powder layer of the negative electrode composite material powder 1 / the compressed powder layer of the solid electrolyte powder 1 / the compressed powder layer of the positive electrode composite material powder 1 in sequence was taken out using a punching machine, and the excess liquid components that seeped out were wiped off.

[0491] <Manufacturing of compressed powder type secondary battery>

[0492] A 50 μm thick Al foil (negative electrode side collector layer) punched into a diameter of 10 mm was placed on a 10 mm diameter SUS table of a solid-state battery evaluation cell (trade name: KP-SolidCell) manufactured by Hohsen Corp., and the compressed powder molded body obtained above was placed on it with the negative electrode side facing downward. A Teflon tube with an inner diameter of 10.2 mm was inserted, and a 50 μm thick Al foil (positive electrode side collector layer) punched into a diameter of 10 mm was placed through a hole in the upper part of the Teflon tube, and a 10 mm diameter, 2 mm thick ground Ti plate was placed thereon, and a 10 mm diameter, 2 cm high Ti rod was placed and placed on the Ti plate.

[0493] Next, the upper shell of KP-SolidCell was embedded and sealed with double O-rings, four-point bolts and butterfly nuts. The cell B was constrained from top to bottom with a torque of 9Nm (equivalent to 60MPa) by the constraint pressure applying mechanism laid on the upper part of KP-SolidCell. Here, cell B refers to a cell formed by stacking the negative electrode side collector layer / compressed powder molded body / positive electrode side collector layer in sequence.

[0494] Next, the KP-SolidCell was temporarily opened and the battery cell B was taken out. After wiping off the excess liquid components that had seeped out due to the application of the restraining pressure, the battery cell B was again placed in the KP-SolidCell in the same manner as above, and the restraining pressure was applied with a torque of 9 Nm (equivalent to 60 MPa).

[0495] Then, with the upper cover open, the internal moisture of the battery cell B was fully removed by freeze vacuum drying for 2 hours. After taking out the KP-SolidCell from the vacuum dryer, the upper cover was closed and sealed with a double O-ring. The compressed powder type secondary battery C was prepared by leaving it at room temperature for 40 hours. In the compressed powder type secondary battery C, the thickness of the positive electrode active material layer is 100μm, the thickness of the solid electrolyte layer is 200μm, and the thickness of the negative electrode active material layer is 100μm.

[0496] Table 6 summarizes the structure of the secondary battery and the evaluation results of the charge and discharge test.

[0497] (Charge and discharge test)

[0498] The coated secondary battery obtained above was subjected to a restraining pressure (30 MPa), and 580-NOHFR (trade name) manufactured by TOYO Corporation was used as a charge and discharge device at a temperature of 27°C, and charging and discharging were repeated under the following conditions. In addition, the compressed powder secondary battery obtained above was subjected to repeated charging and discharging under the following conditions in the same manner as the coated secondary battery, except that the restraining pressure was changed to 60 MPa.

[0499] Charging at a constant current value I β This was continued until the battery voltage reached a desired value of 2.8 V, and after reaching 2.8 V, the voltage was kept constant (2.8 V) until the current value reached 2.4 C.

[0500] After charging, open the circuit and leave it for 10 minutes, then β Discharge is performed until the battery voltage reaches 1.5V.

[0501] The charge and discharge up to this point are defined as one cycle.

[0502] After the discharge, the circuit was opened and left to stand for 10 minutes before the next charge. The charge and discharge were repeated under the same conditions.

[0503] In the above-mentioned charging and discharging, as the initialization of the battery, the current value I β The charge and discharge cycle test was performed by setting the charge to 0.2C and setting the charge and discharge to 3C in the subsequent charge and discharge.

[0504] Then, the discharge capacity retention rate (%) was calculated by the following formula and evaluated according to the following evaluation criteria.

[0505] Discharge capacity retention rate (%) = (discharge capacity after 50 cycles of 3C charge and discharge / discharge capacity after 10 cycles of 3C charge and discharge) × 100

[0506] -Evaluation Criteria-

[0507] A: The discharge capacity retention rate is 70% or more.

[0508] B: The discharge capacity retention rate is 40% or more and less than 70%.

[0509] C: The discharge capacity retention rate is less than 40%.

[0510] [Table 6]

[0511]

[0512] From the above Table 6, it can be confirmed that the secondary battery of the present invention having the solid electrolyte layer containing the solid electrolyte (I) exhibits excellent charge and discharge cycle characteristics and functions as a secondary battery.

[0513] Thus, although the secondary battery of the present invention uses an oxide-based solid electrolyte, the bonding between the particles is excellent, and a collector layer using a metal that is difficult to use under high-temperature sintering conditions can be used. In addition, through the manufacturing method of the secondary battery of the present invention, although an oxide-based solid electrolyte is used, the bonding between the particles is excellent, and a secondary battery using a collector layer using a metal that is difficult to use under high-temperature sintering conditions in an atmosphere containing oxygen can be manufactured.

[0514] The present invention has been described together with its embodiments, but unless otherwise specified, it is understood that the present invention should not be limited to any details in the description and should be broadly interpreted within the scope of the spirit of the invention shown in the attached technical solutions.

[0515] This application claims priority based on Japanese Patent Application No. 2022-089962 filed in Japan on June 1, 2022, the contents of which are incorporated herein by reference as a part of what is described in this specification.

[0516] Explanation of symbols

[0517] 1-negative electrode collector layer, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector layer, 6-working part, 10-all-solid-state lithium-ion secondary battery.

Claims

1. An all-solid-state lithium-ion secondary battery having at least one layer of a laminate, wherein the laminate is sequentially configured with a positive electrode layer, a solid electrolyte layer and a negative electrode layer, in, At least one of the positive electrode layer and the negative electrode layer includes a current collector layer, At least one of the current collector layers is a layer having a metal that melts at 670° C. under normal pressure as a constituent material, or a layer having the metal in a coating layer, The solid electrolyte layer includes an amorphous solid electrolyte, the amorphous solid electrolyte contains a lithium-containing oxide containing Li, B and O, water and a lithium salt, in which the ratio of the content of the lithium salt to the content of the lithium-containing oxide is 0.001 to 1.5 in molar ratio, and the ratio of the content of the water to the content of the lithium-containing oxide is 1 to 12 in molar ratio.

2. The all-solid-state lithium-ion secondary battery according to claim 1, in, The metal melted at normal pressure and 670° C. is Al or Al alloy.

3. The all-solid-state lithium-ion secondary battery according to claim 1 or 2, in, The lithium-containing oxide comprises Li 2+x B 4+y O 7+z , Among them, -0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.

3.

4. A method for manufacturing an all-solid-state lithium-ion secondary battery, wherein the all-solid-state lithium-ion secondary battery has at least one layer of a laminate, wherein the laminate is sequentially configured with a positive electrode layer, a solid electrolyte layer and a negative electrode layer, in, At least one of the positive electrode layer and the negative electrode layer includes a current collector layer, At least one of the current collector layers is a layer having Cu as a constituent material or a layer having Cu in a coating layer, The solid electrolyte layer includes an amorphous solid electrolyte, the amorphous solid electrolyte contains a lithium-containing oxide containing Li, B and O, water and a lithium salt, in which the ratio of the content of the lithium salt to the content of the lithium-containing oxide is 0.001 to 1.5 in terms of molar ratio, and the ratio of the content of the water to the content of the lithium-containing oxide is 1 to 12 in terms of molar ratio, The method for manufacturing an all-solid-state lithium-ion secondary battery includes the step of manufacturing a stack of the positive electrode layer, the solid electrolyte layer, and the negative electrode layer in an atmosphere containing oxygen at 300° C. or lower.